Antimicrobial Resistance, Metal Tolerance, and Virulence Determinants in Gram-negative Opportunistic Pathogens Isolated from Brazilian Groundwater - Rafael da Silva Rosa; Micaela Santana Ramos; Letícia Franco Gervasoni; Lucas David Rodrigues dos Santos; Eduardo Angelino Savazzi; João Pedro Rueda Furlan; Eliana Guedes Stehling (Water, Air, & Soil Pollution, 2026)
Groundwater is a critical freshwater resource, but its quality can be compromised by anthropogenic contamination. Metals may exert selective pressure on microbial communities, promoting metal-tolerant bacteria carrying metal tolerance genes (MTGs), which are often associated with antimicrobial resistance genes (ARGs) and virulence determinants. Therefore, this study aimed to investigate Gram-negative opportunistic bacteria from groundwater, focusing on antimicrobial resistance (AMR), metal tolerance, and virulence profiles. A total of 101 groundwater samples were collected from 58 cities in São Paulo State, Brazil. Physicochemical analyses revealed that some samples exceeded recommended limits for metals, dissolved solids, fluoride, total coliforms, or E. coli . For these samples, 66 bacterial isolates were recovered, including Pseudomonas aeruginosa , Acinetobacter baumannii , Stenotrophomonas maltophilia , Burkholderia cepacia complex, Klebsiella pneumoniae species complex, and Enterobacter hormaechei . Antimicrobial susceptibility testing revealed diverse AMR profiles, with five isolates classified as multidrug-resistant. The ARGs qnrS , bla TEM , aac(6')-Ib , aadA , and tetB were detected. Metal tolerance assays showed tolerance mainly to silver, arsenic, and mercury, with multimetal tolerance detected in several isolates. A wide diversity of MTGs was identified, including silA , pcoA , merA , znuA , and rcnA . Virulence genes related to biofilm formation, immune evasion, and invasion were detected in clinically relevant species. Molecular typing revealed two novel sequence types, P. aeruginosa ST6404 and A. baumannii ST3355, along with clinically associated lineages such as A. baumannii ST744 and K. pneumoniae ST1536. These findings highlight groundwater as a potential environmental reservoir of opportunistic pathogens carrying ARGs, MTGs, and virulence determinants, reinforcing the importance of monitoring these ecosystems to mitigate AMR.

Tracking forest carbon and growth in large-scale passive restoration using multi-temporal airborne lidar - Felipe N. Begliomini; Fabian Jörg Fischer; Srinivasan Keshav; Pedro H.S. Brancalion; Paulo G. Molin; Angelica M. Almeyda Zambrano; Angélica Faria de Resende; Cassio Toledo; Catherine Torres de Almeida; Danilo Roberti Alves de Almeida; Davi Ernesto Alvarenga César; Eben N. Broadbent; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Bioinspired pullulan-based adhesive coacervate films for targeted buccal delivery of peptides - Margarida M.A. Sacramento; Nazanin Z. Ezazi; Eleftheria Pantazoglou; Philip Mark Lund; Marco van de Weert; Zhongyang Zhang; Rui Vitorino; Floriane Bahuon; Ragna Berthelsen; Stephen T. Buckley; Gavrielle R. Untracht; Peter Eskil Andersen; et al. (Carbohydrate Polymers, 2026)

A meta-analysis of the agronomic benefits of silicate rock powders in Brazil in the context of a novel classification - Philipp Swoboda; Eder de Souza Martins; Gisele Freitas Vilela; Giuliano Marchi; Luis Ferreira; Carlos Augusto Posser Silveira; Mariane Chiapini; Marcella Daubermann; Mayra Maniero Rodrigues; Matthew O. Clarkson; Junyao Kang; Veronica Furey; et al. (Geoderma Regional, 2026)

Mapping the unknown: Dark diversity and Wallacean gaps in Neotropical bats (Mammalia: Chiroptera) - Rafaela Jemely Rodrigues Alexandre; Leticia Lima Correia; María Magdalena Ramírez-Martínez; Livia Leon Paniagua; M. Alejandra Camacho; Albert David Ditchfield; Ludmilla Moura de Souza Aguiar; Thiago Bernardi Vieira (Biological Conservation, 2026)

A data-driven gap-filling approach to assess long-term streamflow trends across Colombia - David Antonio Jimenez Osorio; Alvaro Avila-Diaz; Bruno Melo Brentan; André Ferreira Rodrigues; Benjamin Quesada (Hydrological Sciences Journal, 2026)

Multi-agent simulation of Sphenophorus levis infestation and natural biological control with Beauveria bassiana and Steinernema brazilense in sugarcane cultivation - Rayanna Barroso de Oliveira Alves; Diego Bogado Tomasiello; Cláudia Maria de Almeida; David Luciano Rosalen; Luiz Henrique Pereira; Hernande Pereira da Silva; Cesar Leandro Rodrigues (Ecological Modelling, 2026)

Tissue-specific oxidative responses and recovery following acute thermal stress in juvenile Amazonian fish Colossoma macropomum - Naiara Melo; Isaac Konig; Eduarda Rodrigues Barbosa; Stefania Priscilla de Souza; Sidney dos Santos Silva; Ronald Kennedy Luz; Priscila Vieira Rosa; Luis David Solis Murgas (Fish Physiology and Biochemistry, 2026)
Colossoma macropomum (tambaqui) is an economically important Amazonian fish increasingly exposed to heatwaves in tropical aquaculture systems. However, multi-tissue responses to acute thermal stress and recovery remain poorly understood. Juveniles were exposed to 34 °C for 24 h, with samples collected at baseline and at 1, 24, and 48 h post-recovery (28 °C). Antioxidant responses and oxidative damage markers were evaluated to determine whether tambaqui re-establishes physiological homeostasis following acute heat shock. Antioxidant enzymes showed significant time- and tissue-dependent changes following acute heat shock. Overall, SOD, CAT, GPx, GR, and GST activities were transiently altered during the early recovery phase (1–24 h), but most enzymes returned to baseline levels within 48 h in the brain, gills, intestine (except CAT), liver, and muscle (except SOD) (p > 0.05). Regarding oxidative damage markers (PC and MDA), the intestine was the most affected tissue, with significantly higher levels at 48 h than at baseline. Based on integrated biomarker analysis (IBRv2), gills and muscle showed the smallest deviation from baseline levels after 48 h, indicating a more complete recovery compared to the other tissues. The intestine, on the other hand, showed persistent oxidative damage markers even at 48 h of recovery. Overall, the results indicate that although acute heat shock induces transient, tissue-specific oxidative disturbances, juvenile tambaqui largely restore redox homeostasis within 48 h, with recovery capacity varying among tissues.

Selection and Characterization of Novel Glucuronoxylomannan-Mimetic Peptides for Potential Diagnosis of Cryptococcosis - Paulo Roberto da Silva; Kássia Gonçalves de Castro; David Nascimento Silva Teixeira; Carlos Ueira Vieira; Luiz Ricardo Goulart Filho; Alexandre de Paula Rogério; Jussara Gonçalves Vieira; Luciano Pereira Rodrigues (International Journal of Peptide Research and Therapeutics, 2026)
Cryptococcus neoformans is an encapsulated fungal pathogen characterized by a thick polysaccharide capsule, primarily composed of glucuronoxylomannan (GXM), which represents its major virulence factor and a key target for immunodiagnosis. Mimetic peptides that reproduce GXM epitopes may provide standardized, stable alternatives to native polysaccharide antigens for diagnostic and therapeutic applications. This study aimed to identify and characterize novel GXM-mimetic peptides using phage display technology and evaluate their potential as synthetic reagents for the serological diagnosis of cryptococcosis. Phage display biopanning was performed through three successive cycles using a Ph.D.-7™ combinatorial library against the anti-GXM monoclonal antibody (mAb) 18B7. Selected phage clones were sequenced, and the predominant peptide motif was identified. Based on the consensus sequence, three variants were designed: a linear peptide (LP), a cyclic peptide (CP), and a double-cyclic peptide (DP). Their immunoreactivity and diagnostic performance were evaluated via enzyme-linked immunosorbent assay (ELISA), including dose-response, serum reactivity across clinical cohorts (active cryptococcosis, treated patients, and healthy controls), and competitive inhibition assays against native GXM. Biopanning resulted in significant enrichment, with the peptide PPSLYWL (CryMab 1) emerging as the predominant sequence (54.8% frequency). ELISA demonstrated dose-dependent binding of the synthetic variants to mAb 18B7 and effective discrimination between sera from active cryptococcosis patients and control groups. In competitive ELISA, the LP variant successfully inhibited antibody binding to native GXM by 50.86%, confirming its functional antigenic mimicry. The identified GXM-mimetic peptides, particularly the LP and CP variants, exhibit specific immunoreactivity and diagnostic utility. These findings support their potential as standardized, low-cost alternatives to native fungal antigens in cryptococcosis diagnosis and provide a basis for future peptide-based theranostic strategies.

Environmental Drivers of Spatial Distribution of Two Sympatric Blue Crabs (Callinectes danae and C. sapidus), Key Fishery Resources in a Subtropical Brazilian Estuary - Sara Abrão Tembe; David Valença Dantas; Jorge Luiz Rodrigues-Filho; Bárbara Heck Schallenberger; César Augusto Forti Reis; Eduardo Döbber Vontobel; Fábio G. Daura-Jorge; Andrea Santarosa Freire; Luis Carlos-Pinto (Estuaries and Coasts, 2026)

In silico analysis of cholesterol binding to species-specific and non-specific albumins and their effects on in vitro quality parameters of ram spermatozoa - Eduardo Rodrigues Pessoa; Cristina Palacin-Martinez; Victor Lucas Bernardes França; Marta Neila-Montero; Rafael Montes-Garrido; David Ramírez-González; Caio Bruno de Lima Oliveira; Denise Damasceno Guerreiro; Mercedes Álvarez; Luis Anel; Luis Anel-Lopez; Valder Nogueira Freire; et al. (Animal Reproduction Science, 2026)

Connectivity of the Blue Crab Callinectes sapidus in the Southwest Atlantic Ocean: Population Genetics, Biophysical Modeling and Management Implications - Erika Meerhoff; Noemi Rojas‐Hernández; David Véliz; Marcos Alaniz Rodrigues; Vincent Combes; Ricardo Matano; Omar Defeo (Marine Ecology, 2026)
Bio‐oceanographic modeling and population genomics were combined to assess connectivity of the blue crab Callinectes sapidus in the Southwestern Atlantic Ocean, with particular attention to the scale of its fishery management, and the potential role of Marine Protected Areas (MPAs) in Uruguay as larval source zones. A bio‐physical model, coupled with hydrodynamic outputs of a model experiment, incorporated larval vertical migration behavior and key species‐specific traits to simulate dispersal pathways across the region. Population structure was assessed by using SNPs variability. Both approaches revealed substantial connectivity among sampled locations. Genomic population genetic analysis supported a single, well‐mixed population across the study area, consistent with the extensive dispersal predicted by the model. These results highlight the need for management strategies tailored to the species' population structure and emphasize the importance of binational (Brazil‐Uruguay) coordination for this transboundary fishery, which is already showing clear signs of overexploitation. Model simulations further showed that Uruguayan MPAs may act as important larval sources, particularly during winter recruitment under La Niña conditions, exporting propagules to non‐protected areas in southern Brazil. By resolving the spatial and temporal scales of larval exchange, this study enhances regional understanding of connectivity patterns and supports evidence‐based conservation planning for C. sapidus .

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Chemical analysis and biological activity of crude extracts obtained from leaves of Passiflora foetida (Subg. Passiflora ) and Passiflora morifolia (Subg. Decaloba) - Ohana Luiza Santos de Oliveira; Oscar Caetano da Silva Neto; Gabriele Rodrigues Conceição; Fábio Alexandre Chinalia; Daniel Pereira Bezerra; Milena Botelho Pereira Soares; Valdenizia Rodrigues Silva; Luciano de Souza Santos; Carla Junqueira Moragas Tellís; João Victor da Silva e Silva; Caroline Conceição da Guarda; Jorge Mauricio David; et al. (Natural Product Research, 2026)

Dynamic stability in phytoplankton through size-based compensation under ENSO extremes - Luciane Oliveira Crossetti; Kauane Bordin; Andressa da Rosa Wieliczko; Rafael Cecchi Sabbadin; Maria Gabriela Junqueira; Lucia Ribeiro Rodrigues; David da Motta‑Marques (Hydrobiologia, 2026)
Climatic extremes associated with the El Niño–Southern Oscillation (ENSO) reorganize aquatic communities, but whether such reassembly translates into functional restructuring remains unclear. A 25-year phytoplankton time series (2001–2025) from Lake Mangueira, a large subtropical shallow lake in southern Brazil, was used to test whether El Niño and La Niña drive shifts in size-based functional structure or primarily taxonomic turnover. The findings of this study provide novel insights into the organization of the phytoplankton size-based functional structure based on long-term continuous datasets under climatic events in a subtropical shallow lake. ENSO phases imposed contrasting environmental filters, with El Niño linked to increased precipitation and La Niña to drought, differing in transparency and nutrient concentrations. Species composition changed markedly across climatic phases, yet total biomass and overall functional configuration remained stable. Functional redundancy and taxonomic diversity increased during La Niña, while functional diversity patterns varied according to the metric (biovolume or maximum linear dimension) considered. The observed functional shifts resulted from species replacement along environmental gradients rather than from systematic redistribution of trait values. ENSO thus reshaped internal community structure without triggering regime shifts during regular periods, revealing dynamic stability sustained by size-based compensatory mechanisms.

The synergistic effect of H2O2 and indole-3-butyric acid on Cordia trichotoma rooting does not overcome aging effects of older mini-stumps - Maria Clara Coutinho Rodrigues; Ana Carolina Nascimento de Oliveira; Giovanna Campos Mamede Weiss de Carvalho; Jussara Tamires de Souza Silva Goulart; David Pessanha Siqueira; Deborah Guerra Barroso (Rhizosphere, 2026)

Too close for comfort? Mesozooplankton dynamics in Marine Protected Areas adjacent to mining tailings on the southeastern Brazilian shelf - Bianca Salvador; Laura Rodrigues da Conceição; Renato David Ghisolfi; Mônica Souza Mendes; Tayná Rosa Martins Paiva; Valéria da Silva Quaresma; Daniel Rigo; Gustavo Martins Rocha; Paulo Sergio Salomon; Gabriel Harley Costa Santos; Priscila Teixeira-Amaral; Márcio Murilo Barboza Tenório; et al. (Marine Environmental Research, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Impact of Water Deficit Stress on Starch Characteristics in Potatoes: An Integrative Perspective of Physiological, Biochemical, and Molecular Mechanisms - Andres Felipe Gaona Acevedo; Juan David Ferreira Gomes; Juliana Nascimento Rodrigues; Matheus França Gonçalves; Gabriel Oliveira Ferreira; Rogerio Lopes Vieites (Potato Research, 2026)
Among the most cultivated crops worldwide, potato ( Solanum tuberosum) faces significant threats from water scarcity, owing to its shallow root system and high irrigation requirement. Water deficit disturbs homeostasis and critical physiological mechanisms, including photosynthesis, carbohydrate translocation, and starch metabolism in tuberous plants. It reduces CO₂ assimilation, modulates the expression of key enzymes involved in starch synthesis, such as ADP-glucose pyrophosphorylase and starch synthases, and alters the amylose–amylopectin ratio, consequently affecting their rheological properties. Additionally, drought triggers antioxidant and metabolic responses in plants, including the accumulation of secondary metabolites and the regulation of stress tolerance-related genes. Transcriptomic analyses have revealed water-deficit responsive genes, such as StMAPK11 , StCDPK13 , and StERF94 , which contribute to stress adaptation. This review also explores mitigation strategies and genetic improvement approaches, including the application of biostimulants (chitosan, uniconazole), ZnO and SiO₂ nanoparticles, and the selection of more drought-tolerant genotypes. Recent advances in biotechnology, including gene editing and omics technologies, have contributed to the development of stress-resilient potato varieties.

Mapping Escolar ( Lepidocybium flavobrunneum ) in Motion: Oceanographic Forces Shaping Its Habitat in the Southwestern South Atlantic, With Insights From Fishers' Perceptions - Lucas Rodrigues; Maria Grazia Pennino; Paul Gerhard Kinas; David Conesa; Alba Fuster‐Alonso; Andrés Domingo; Rodrigo Forselledo; Federico Mas; Bruno Mourato; Rodrigo Sant'Ana; Vinni Santos Thykjaer; Raquel Virginia Marquez Marquez; et al. (Fisheries Oceanography, 2026)
Lepidocybium flavobrunneum [Smith, 1843], commonly known as escolar, is a large pelagic species, important for global and local fisheries, particularly in the southwestern South Atlantic Ocean (SWAO), where it constitutes a significant portion of the catch. However, despite its important socioeconomic role, it remains less studied compared to other large pelagic species. Enhancing research efforts is therefore key to better understanding the ecological processes that influence its spatial and temporal distribution. To address this gap, our study applied species distribution models (SDMs) to escolar's occurrence and abundance using longline fleet data from south Brazil and Uruguay. Estimation and prediction were conducted at the Bayesian framework using the integrated nested Laplace approximation (INLA) methodology combined with the stochastic partial differential equation (SPDE) approach. Our findings reveal a strong correlation between warmer sea surface temperatures and increased escolar occurrence and abundance in the SWAO, particularly during the austral summer, in contrast to cooler‐season patterns observed elsewhere. Escolar's distribution is influenced by the southward and westward movement of seawater driven by the Brazil Current, and its preference for depths greater than 2000 m reflects its oceanic nature. Predicted areas of higher abundance around the continental slope (between 33° and 37° S) and the Rio Grande Rise are linked to the dynamic interaction of warm and cold currents and nutrient‐rich waters. Additionally, escolar's sensitivity to low‐light conditions may explain reduced catches during moonlit nights. A complementary analysis assessing the synergistic influence of sea surface temperature and lunar illumination on escolar occurrence indicated that, under high temperatures (> 22 °C), occurrence is further enhanced during dark nights. Furthermore, semi‐structured interviews with vessel captains revealed that 90% identified temperature (via open‐ended responses) as a key environmental factor driving escolar catches, and 80% of them attributed a strong influence (greater than average catch rates) to temperature, summer season and new moon phase. This study provides new insights into escolar's seasonal and spatial patterns, emphasizing the impact of oceanographic features and light conditions on its distribution. It also highlights the need for further research into the mechanisms driving escolar populations.

Integration of Multi-Omics Data To Understand the Multifaceted Role of RAMP1 across Different Cancer Types - Gabrielle da Costa Cabral; Letícia Almeida Rodrigues; Júlia de Almeida Cabral Candiago; João Felipe Fernandes Ferreira Procópio; Júlia Costa Cerqueira Silva; Maria Eduarda Barbosa de Lima; Ana Stella Gisela Ellery Costa Lima; José Valmir Falcão da Costa Júnior; David Abner Santos de Araújo; João Paulo Emiliano da Silva; Sofia Amancio de Almeida Oliveira; Rafael de Oliveira Calaça Farias; et al. (Cell Biochemistry and Biophysics, 2026)
Receptor Activity-Modifying Protein 1 (RAMP1) is a Calcitonin Receptor-Like Receptor (CALCRL)-associated protein with significant relevance in oncogenesis and tumor progression. It acts as a context-dependent allosteric modulator of GPCRs. This integrative review synthesizes evidence from multiple omics layers—transcriptomics, proteomics, epigenomics, and pan-cancer datasets—to clarify the role of RAMP1, its signaling pathways, and its relationship with the tumor microenvironment. Multi-omics integration highlighted several key findings: transcriptomic and regulatory signatures frequently associate RAMP1 overexpression with epithelial–mesenchymal transition; RAMP1 is associated with the coordinated activation of GPCR-dependent pro-tumorigenic pathways; and the CGRP/RAMP1 axis is associated with CD8 + T-cell exhaustion and potential resistance to immune checkpoint inhibitors. Pan-cancer analyses revealed marked expression heterogeneity. RAMP1 is strongly overexpressed in hepatocellular carcinoma (LIHC) and downregulated in kidney renal clear cell carcinoma (KIRC), reinforcing the importance of context-specific interpretation. It also emerges as an unfavorable prognostic biomarker in osteosarcoma, rectal adenocarcinoma, prostate cancer, and Ewing sarcoma, suggesting its potential value as a strategic therapeutic target. Future studies should prioritize spatial transcriptomics and the pharmacological modulation of the CGRP/RAMP1 axis to refine precision oncology strategies.

Phylogenetic diversity recovery along Atlantic Forest succession: The potential for conserving evolutionary history - Alex Josélio Pires Coelho; Carlos Mário Galván-Cisneros; Pedro Manuel Villa; Heitor Mancini Teixeira; Fabio Antônio Ribeiro Matos; Alice Cristina Rodrigues; Nayara Mesquita Mota; Fernando da Costa Britod Lacerda; Fábia Maria dos Santos Souza; Nathália Vieira Hissa Safar; Nathália Silva; Fabiana Bonani; et al. (Biological Conservation, 2026)

Circular and Sustainable Business Model Innovation: Formulating an Integrated Concept Through A Systematic Literature Review - Andreza Rodrigues de Araujo; Rodrigo Marques de Almeida Guerra; David Lorenzi Junior; Jordana Marques Kneipp; Luísa Margarida Cagica Carvalho (Circular Economy and Sustainability, 2026)
Despite the significant growth in research on the triad of Circular Economy (CE), Innovation, and Sustainable Business Models (SBMs), theoretical fragmentation persists due to the lack of holistic conceptual integration, resulting in a heterogeneous framework that is difficult to apply in practice. Given this scenario, this study aimed to identify, categorize, and systematize the state of the art of Circular Economy, Innovation, and Sustainable Business Models, aiming to increase conceptual clarity and strengthen the application of these concepts in theory and practice. At the same time, we sought to map emerging trends, opportunities, challenges, and future directions capable of supporting the work of academics, practitioners, and public policymakers. To this end, we conducted a systematic literature review based on the Scientific Procedures and Rationales for Systematic Literature Reviews (SPAR-4-SLR) and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocols, resulting in the final selection of 60 publications extracted from the Scopus database. The results suggest that research in this field is emerging, rapidly expanding, and with increasing diversity of applications across different contexts and sectors, although still concentrated in developed countries and at an early stage of scientific maturity, marked by the predominance of systematic reviews and case studies. A thematic evolution was also observed, moving from a focus on climate change and energy efficiency to encompass design principles, cross-sector collaboration, and sectors such as the bioeconomy and recycling, in addition to the more recent incorporation of digital technologies and consumer-focused strategies. Based on the analysis, the concept of Circular and Sustainable Business Model Innovation (CSIBI) is proposed, integrating the triad and systematizing its conceptual basis. The future research agenda covers strategies and metrics for sustainable circularity, as well as the role of digital technologies, governance, and human factors, providing guidance to consolidate the field. This framework contributes to the advancement of new research, strengthens the adoption of business practices in the transition to more circular and sustainable business models, and provides input for public policymakers, integrating the principles of the circular economy, innovation, and sustainable business models.

Emerging co-occurrence of mcr-10 and broad-spectrum β-lactamase genes in Enterobacterales from surface waters in Brazil - Rafael da Silva Rosa; João Pedro Rueda Furlan; Lucas David Rodrigues dos Santos; Micaela Santana Ramos; Eduardo Angelino Savazzi; Eliana Guedes Stehling (Environmental Monitoring and Assessment, 2026)
Aquatic ecosystems play a key role in the spread of antimicrobial resistance genes (ARGs), especially mcr -type and β-lactamase genes. The occurrence of β-lactamases and the mcr-10 genes has emerged among Enterobacterales species across the world; however, this phenomenon had never been reported in Brazil until now. We performed a surveillance study focusing on the spread of the mcr -type genes in WHO critical bacterial priority pathogens isolated from aquatic ecosystems. For this, 132 surface water samples from rivers and streams were collected between 2021 and 2023 and studied, and 492 bacterial strains were obtained. Accordingly, 14 strains (11 Escherichia coli and three Klebsiella pneumoniae species complex) resistant to third-generation cephalosporins or carbapenems were identified as harboring the mcr-10 gene. These strains belonged to international, unusual, and novel clones. In addition, several ARGs were detected, spotlighting ESBL- and carbapenemase-encoding genes, which confer resistance to clinically important antimicrobials. Most virulence genes and plasmid replicons were found, and two novel multireplicon plasmids were identified in a Klebsiella quasipneumoniae strain. These findings highlight the first report of the mcr-10 gene in Brazil and the early dissemination throughout the environmental sector. Therefore, the identification of Enterobacterales strains co-producing mcr-10 and broad-spectrum-β-lactamase genes draws attention to a new trend in antimicrobial resistance mediated by critical pathogens in the environment.

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Origin, viability, and cell cycle status of seminal somatic cells for potential application in cattle cloning via nuclear transfer - Higor da Silva Ferreira; Gabriella Borba de Oliveira; Eduardo de Oliveira Sanguinet; Ana Laura da Silva Feijó; César Augusto Pinzón-Osorio; Verônica Rafaela Benvenutti; Louise Fontoura Köhler; Marianna Bertolini; Fernando Almeida-Souza; Felipe de Jesus Moraes Junior; David Driemeier; Ana Lúcia Abreu-Silva; et al. (Reproductive Biology, 2026)

Modeling of Listeria monocytogenes and Staphylococcus aureus behavior in salted and cured meat products - Matheus P.S. Láscaris; Jaqueline S. Correia; Dionisio P. Amorim-Neto; Beatriz D.P. Machado; Emilie Lang; Leonardo P. Silva; Augusto C.C. Santos; Juliana A.L. Pallone; David S. Costa; Camila A. Akiyama; Adriana P.A. Bragotto; Mayana A.R.V. Tomaz; et al. (International Journal of Food Microbiology, 2026)

Photon Flux and Water Matrix Effects in Sn-Doped Ti-Zr Oxide Photocatalysts: Transformation Products and Phytotoxicity - Louidi Lauer Albornoz; Juan Pablo Bortolozzi; Ezequiel David Banús; Salatiel Wohlmuth da Silva; Diego Umberto Rizzana; Maria Genesi Meirelles; Marco Antônio Siqueira Rodrigues; María Alicia Ulla; Andréa Moura Bernardes (Water, Air, & Soil Pollution, 2026)

Ecodesign of collagen extraction from tilapia skin: an integrated economic–environmental framework for process and product improvement at the laboratory scale - Johnny David Gomes de Queiroz; Ednaldo Benício de Sá Filho; Maria do Livramento Linhares Rodrigues Menezes; Gabriela Ibiapina Figueiredo Câmara; Men de Sá Moreira de Souza Filho; Raimundo Marcelino da Silva Neto; Renato Carrha Leitão; Maria Cléa Brito de Figueirêdo (The International Journal of Life Cycle Assessment, 2026)
Purpose Tilapia skin, a filleting by product, can be used to extract collagen (CTS) for bio-based films and hydrogels. This study performs the first ex-ante environmental and economic assessment of CTS, evaluating two pathways for these applications, with the aim of guiding the selection of one of these pathways for future investments in pilot plants or their redesign. Methods Two pathways for extracting 1 kg/year of CTS were modeled at a pilot scale using laboratory data in SuperPro Designer: acid-soluble (ASC) and pepsin-soluble (PSC). Total costs and the Product Environmental Footprint were combined in contribution and scenario analyses, considering the mass and economic allocation in tilapia production and filleting. The contributions of unit processes to the impacts and costs of CTS were shown in a proportionality graph with a threshold line of relevance; only the critical points above it were prioritized to identify alternatives to reduce environmental and/or economic impacts. An optimal pathway was selected, considering uncertainty. The impacts of CTS (optimal pathway) were then compared to those of cellulose, starch, and polyacrylamide, used in films and hydrogels. The minimum selling price (MSP), calculated as annual costs per production, was also compared to surrogate market prices. These comparisons included sensitivity and uncertainty analyses. Results and discussion The CTS performance study shows that collagen has greater environmental and price impacts than cornstarch, cellulose, and polyacrylamide, even with 90% less CTS, in both allocation criteria and in most impact categories. The comparison between ASC and PSC after improvements reveals that ASC outperforms PSC, leading to its selection. In both pathways and criteria, the main critical points above the relevance threshold and close to the proportionality line are sodium chloride, ultrapure water, acetic acid, and ethanol. For these points, the most effective alternatives are replacing dialysis with diafiltration and adjusting the acetic acid concentration, along with reducing reaction time, temperature, and yield. Conclusions Recommendations were provided for redesigning the CTS production process and its targeted application, highlighting potential improvements such as the use of electrodialysis in the purification stage, the removal of the lipid extraction step or the replacement of ethanol with butyl alcohol, as well as the evaluation of applications in the biomedical sector. Learnings from this study allowed the proposition of a novel integrated framework for improving technological pathways and targeting product application based on techno-economic and environmental impact criteria at technology readiness level 5. This framework may be applied to assess and improve other technologies on a laboratory scale.

Differential effects of adolescent fatty acid amide hydrolase and monoacylglycerol lipase inhibition on adolescent and adult behaviors in male rats - Mary K. Estes; Vishnu Guda; Emei Thompson; Daniela Rodrigues de Oliveira; David B. Nowak; Cecilia J. Hillard; John R. Mantsch (Psychopharmacology, 2026)

Synchronous Miocene radiations and geographic-dependent diversification of pantropical Xylopia (Annonaceae) - Francis J. Nge; David M. Johnson; Nancy A. Murray; Laura Holzmeyer; Keegan Floyd; Gregory Stull; Vincent R.C. Soule; Pierre Sepulchre; Delphine Tardif; Carlos Rodrigues-Vaz; Thomas L.P. Couvreur (Molecular Phylogenetics and Evolution, 2026)

Cork stripping alters the seasonal carbon allocation patterns of Quercus suber in a dry year - Clara A. Pinto; Filipe Costa-e-Silva; Alexandra C. Correia; José Graça; Olfa Zarrouk; Teresa S. David; José C. Rodrigues; João S. Pereira; Maria Manuela Chaves; Carla Pinheiro (Forest Ecology and Management, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Tree cover influences bird assemblage composition in a city within the cerrado biodiversity hotspot - Daniele Pereira Rodrigues; David P. Edwards; Ana Claudia Almeida; Mauricio Almeida-Gomes (Urban Ecosystems, 2026)

Multi-temporal scale of urban rainfall in the Eastern Northeast based on observed data and gridded products: physiographic factors and changes in land use and occupation - Luis Felipe Francisco Ferreira da Silva; William Max de Oliveira Romão; Gustavo Bastos Lyra; Elania Barros da Silva; Micejane da Silva Costa; David Mendes; Munawar Shah; Rasim Shahzad; Danilo Siden Batista Santos Silva; Mônica Dayana Albuquerque Tenório; Ricardo Victor Rodrigues Barbosa; Sudhir Kumar Singh; et al. (Natural Hazards, 2026)

Environmental occurrence of optrA-mediated linezolid resistance in Enterococcus isolates and genomic insights into Enterococcus faecium ST54 co-harboring optrA, poxtA, and cfr(D) genes - Lucas David Rodrigues Dos Santos; João Pedro Rueda Furlan; Rafael da Silva Rosa; Micaela Santana Ramos; Letícia Franco Gervasoni; Eduardo Angelino Savazzi; Teresa Nogueira; Eliana Guedes Stehling (World Journal of Microbiology and Biotechnology, 2026)
Linezolid-resistant Enterococcus species have emerged worldwide, with resistance mainly driven by plasmid-borne optrA , poxtA , and cfr genes. While the optrA gene has been increasingly identified in humans and animals, its presence in the environmental sector remains poorly studied, especially in South America. This study aimed to investigate and characterize linezolid resistance genes in isolates of Enterococcus faecium and Enterococcus faecalis obtained from aquatic ecosystems in 51 cities in the state of São Paulo, Brazil. Phenotypic, molecular, and genomic analyses were used for this proposal. Accordingly, 181 Enterococcus isolates were obtained, with 67 (37%) harboring the optrA gene. Most isolates exhibited multidrug resistance, and the minimum inhibitory concentration to linezolid ranged from 0.5 to > 64 mg/L. Several virulence genes and plasmid replicons were observed, with gelE and rep 9 being most prevalent, respectively. Ten isolates co-harbored the optrA and poxtA genes and belonged to the known sequence type (ST) 1221 ( E. faecium ) and ST283, ST253, ST234, and ST1230 ( E. faecalis ), as well as to the new ST3018, ST3022, ST3026, and ST3027 ( E. faecium ), and ST2126 ( E. faecalis ). Moreover, one E. faecium isolate (EW1587) carried optrA , poxtA , and cfr (D) genes and, therefore, was submitted to genomic characterization. Isolate EW1587 belonged to ST54 and was closely related to an animal-derived Brazilian strain. In silico analysis predicted that optrA , poxtA , and cfr (D) genes were plasmid-borne, whereas in vitro stability tests demonstrated that these genes remained stable for 30 days. These results highlight the environmental spread of transferable oxazolidinone resistance genes, with E. faecium ST54 co-carrying optrA , poxtA , and cfr (D) genes. Therefore, continuous monitoring is essential to fully elucidate the mechanisms driving the spread and evolution of linezolid resistance across environmental reservoirs.

Acute and chronic effects of salinity on nitrification in a recirculating aquaculture system with açaí seeds (Euterpe oleracea) as biological media - Deyselana Lima da Costa; Bruno José Corecha Fernandes Eiras; Jean Danilo da Silva Pereira; Adriele Carolina Raiol Rodrigues; Hayanna Lucy Barbosa Barros; Glauber David Almeida Palheta; Nuno Filipe Alves Correia de Melo; Maria de Lourdes Souza Santos; João Felipe Nogueira Matias; Fabio Carneiro Sterzelecki (Frontiers in Marine Science, 2026)
Introduction The Blue Amazon represents an extensive coastal zone with high biodiversity and wide salinity variation, which poses challenges for marine fish farming, particularly regarding the efficiency of biofilters in recirculating aquaculture systems (RAS). In this context, açaí seeds ( Euterpe oleracea ), previously evaluated in freshwater, emerge as a promising alternative for use as filter media under different salinity conditions. The objective of this study was to evaluate the potential of açaí seeds as substrate in RAS biofilters, analyzing their acute and chronic impact on the physicochemical parameters of water and the removal of ammonia, nitrite and nitrate over 28 days. Methods The experiment was conducted in six independent systems (three aquaria each), subjected to salinities of 0, 7, 14, 21, 28 and 35‰. After Acute (0, 20, 40, 60,80,100 and 120 minutes) and chronic (2,3,4,14,21 and 28 days) salinity change, water samples were collected to measure physicochemical quality and to assess nitrification efficiency and nitrogen compound removal. Results Higher oxygen consumption and ammonia clearance were observed at 0, 7 and 14‰ after 120 minutes of salinity change, while nitrate accumulation was significantly higher in freshwater. In long term, after 28 days, ammonia clearance was significantly lower at 35‰, though nitrate accumulation was not affected by salinity. The highest ammonia removal rates were recorded in the 0‰ and 7‰ treatments. Discussion The results demonstrate that açaí seeds are capable of removing ammonia after a few minutes and can sustain the growth of nitrifying bacteria under different salinity levels, although more efficiently in low salinity waters (seven times).

Multiple ecotoxicological effects of sublethal exposures to atmospheric particulate matter in two neotropical benthic species - Diego Ferreira Gomes; Thandy Junio da Silva Pinto; David Silva Alexandre; Michelly Pereira Soares; Raquel Aparecida Moreira; Hevelyn Plácido Gomes; Maira Rodrigues Lima; Evaldo Luiz Gaeta Espíndola; Odete Rocha; Marisa Narciso Fernandes (Journal of Hazardous Materials, 2026)

Minocycline Ameliorates Cognitive Impairments Without Modulating Microglial Reactivity in Sporadic Hypercholesterolemia: A Sex-Specific Analysis in Mice - Matheus Scarpatto Rodrigues; Natalia Baltazar do Nascimento; Gabriela Joras Baumart; Taina Schons; Alex Paulo Padilha; Mariana Viana Costa; Hémelin Resende Farias; Lilian Corrêa Costa-Beber; Fernanda Telles Fróes; Ariadni Mesquita Peres; Ricardo Maia Dantas; Alessandra Gonçalves Machado; et al. (Molecular Neurobiology, 2026)

Fine-scale patterns and drivers of ploidy state in lentic and lotic macrophyte assemblages across the world - Tatiana Lobato-de Magalhães; Kevin Murphy; Thomas A. Davidson; Jorge García-Girón; Andrey Efremov; Victor Chepinoga; Eugenio Molina-Navarro; Celeste Franceschini; Roger P. Mormul; Hui Fu; Rossano Bolpagni; Juri Nascimbene; et al. (Aquatic Botany, 2026)

Taxonomic update for the giant algal chloroviruses of the family Phycodnaviridae - Rodrigo A. L. Rodrigues; João Victor R. P. Carvalho; Lethícia R. Henriques; David D. Dunigan; James L. Van Etten (Archives of Virology, 2026)

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Individual and combined effects of a simulated heatwave and the emerging Phytophthora ×multiformis on European alder species - I. Gomes Marques; C. Vieites-Blanco; M.J. Barrento; A. Cupertino; J.N. Semedo; A.P. Rodrigues; P. Scotti-Campos; T. Jung; A. Solla; T.S. David; P.M. Rodríguez-González (Forest Ecology and Management, 2025)

Mycobacterial infections in cats and a dog: A case series from Southern Brazil and one health implications - Bibiana Campello Moglia Dutra; Anelise Bonilla Trindade-Gerardi; Gabriela da Cruz Schaefer; Samara Christina França de Almeida; Bruna Correa Lopes; Cristine Cerva; Deisy Daiana Lerner; Matheus Viezzer Bianchi; Angélica Cavalheiro Bertagnolli Rodrigues; Rogério Oliveira Rodrigues; Gabriela Hartmann; David Driemeier; et al. (Veterinary Research Communications, 2025)

Crop rotation and succession in soybean production systems: cover crop biomass, grain yield and revenue - Leandro Pereira Pacheco; Claudinei Kappes; Andressa Selestina Dalla Côrt; Rayane Gabriel da Silva; Edicarlos Damacena de Souza; Thaís Rodrigues Magalhães Guedes; Laércio Santos Silva; Rafael Felippe Ratke; Fabiano André Petter; João Henrique dos Santos Ferreira; José Roberto Portugal; Ivan David Ferreira Silva; et al. (Plant and Soil, 2025)

Importance of trace elements in the immunometabolic health of people living with HIV/AIDS: a literature review - Sara Souza Rodrigues; Mayara Bocchi; David Michel de Oliveira; Eduardo Vignoto Fernandes (Molecular Biology Reports, 2025)

Shallow-to-mesophotic geomorphic habitats influenced by a drowned incised valley in the Western Equatorial Atlantic - Antonio Rodrigues Ximenes Neto; Lidriana de Souza Pinheiro; Regimário Pereira Lima Filho; David Hélio Miranda de Medeiros; Carlos de Araújo Farrapeira Neto; Marcelo Oliveira Soares; Sérgio Rossi; Jáder Onofre de Morais (Geo-Marine Letters, 2025)

Sugarcane radiation use efficiency: varietal differences, temperature dependence, and implications for modeling biomass across environments - Mathias Christina; David Clark; Fabio Ricardo Marin; Rafael Vasconcelos Ribeiro; Julio Victor Saez; Tendai Polite Chibarabada; Murilo dos Santos Vianna; Matthew R. Jones; Santiago Vianna Cuadra; Osvaldo Machado Rodrigues Cabral; Martin Moises Acreche; Henrique Boriolo Dias (Agricultural and Forest Meteorology, 2025)

Afforestation with tropical N-fixing species in the Brazilian Atlantic rainforest: carbon and nitrogen in the soil profile - David Pessanha Siqueira; Emanuela Forestieri Gama-Rodrigues; Marcos Vinicius Winckler Caldeira; Carlos Eduardo Rezende; Claudio Roberto Marciano; Deborah Guerra Barroso (Acta Oecologica, 2025)

Association of corn processing methods and sodium lasalocid for beef cattle on pasture during the finishing phase - Paloma Helena Gonçalves; Gabriel Santos Souza David; Laura Franco Prados; Bianca Rodrigues Domingos; Beatriz Lima Vellini; Felipe Almeida Nascimento; Willian Manoel Ricardo Foresto; Naiara Caixeta da Silva; Flávio Dutra de Resende; Gustavo Rezende Siqueira (Tropical Animal Health and Production, 2025)

Drivers of carbon accumulation in eucalypt plantations: a multivariate analysis and prediction models for Australian and Brazilian experiments - Juliana Campos Amorim; João Marcos Rebessi de Sousa; Fábio Prataviera; Paulo Henrique Müller da Silva; Sérgio Augusto Rodrigues; Sam Van Holsbeeck; Saulo Philipe Sebastião Guerra; David J. Lee; Humberto de Jesus Eufrade-Junior (New Forests, 2025)

Vitamin D-loaded lipid nanoparticles: antioxidant properties, preparation, optimization, and in vitro characterization - Khadeejeh AL-Smadi; Mohammad Imran; Ayyah Abdoh; David Liu; Khanh Phan; Newton Andreo Filho; Vania Rodrigues Leite-Silva; Yousuf Mohammed (Drug Delivery and Translational Research, 2025)
Vitamin D 3 -loaded lipid nanoparticles (Vit D 3 -LNP), integrated into an azulene cream, were developed to enhance the topical delivery and stability of Vitamin D 3 . The LNP was formulated using a lipid mixture and hot homogenization-ultrasonication, with comprehensive characterization revealing a particle size of 153.9 nm, a high zeta potential (-54.3 mV), and a PDI of 0.216, which TEM confirmed. Encapsulation efficiency was high (96.98%), indicating successful incorporation of Vitamin D 3 within the lipid matrix. Stability studies revealed the impact of light exposure on Vitamin D 3 degradation. In vitro, release, and skin penetration studies using Franz diffusion cells and two-photon microscopy demonstrated enhanced drug permeation and retention in deeper skin layers with the cream formulation. Cell Viability test confirmed high cell viability (~ 80–100%) for both free Vitamin D 3 and the LNP formulation; also inflammation test showed a significant reduction in ROS levels with Vitamin D 3 -LNP treatment. These findings highlight the therapeutic value of LNP in managing conditions like Vitiligo, providing insights into the design of stable, effective Vitamin D 3 delivery systems for dermal applications, and offering a promising approach for advanced skin treatments. Graphical Abstract

Understanding farm-level diversity to guide soil fertility management in West African cotton systems: Evidence from Benin - G.I. Anita Dossouhoui; Pierrot Lionel Yemadje; David Berre; Rodrigue Vivien Cao Diogo; Pablo Tittonell (Agriculture, Ecosystems & Environment, 2025)

A new protocol for genetic transformation of Setaria viridis (L) using morphogenic callus via thin cell layers - Juan David Ferreira Gomes; Juliana Nascimento Rodrigues; Eveline Carla da Rocha Tavano; Adriana Pinheiro Martinelli; Marcio Alves-Ferreira (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Asphalt mixtures with bauxite residue as a partial replacement for fine aggregates: technical, economic, and environmental assessment - Lara Pereira Tavares Mendes; Osires de Medeiros Melo Neto; Leonardo Rodrigues Guedes; Gilson Gabriel Teixeira Varela; Aldenora Vieira Santos Neta; David Braga Fernandes; Leda Christiane de Figueiredo Lopes Lucena; Luciana de Figueiredo Lopes Lucena (Environmental Science and Pollution Research, 2025)

Climate projections indicate a loss and redistribution of the biodiversity of valuable plants in the Brazilian semiarid - Everton A. Maciel; Fabrina Bolzan Martins; José Maria Cardoso da Silva; David Montenegro Lapola; Roger Rodrigues Torres (Journal for Nature Conservation, 2025)

A novel zooplankton-based environmental monitoring tool for coastal impacted areas: The case of the Doce River dam rupture - Gustavo Martins Rocha; Bianca Salvador; Gabriel Harley Costa Santos; Laura Rodrigues da Conceição; Priscila Teixeira-Amaral; Maikon Di Domenico; Diego de Arruda Xavier; Eduardo Schettini Costa; Renata Caiado Cagnin; Cesar Alexandro da Silva; Mayara Bandeira; Mônica de Souza Mendes; et al. (Estuarine, Coastal and Shelf Science, 2025)

Amazonian floodplain lakes’ carbon-based structure and interactions of plankton communities are constrained by hydrology - Luana Morais da Rosa; Luciana de Souza Cardoso; Luciane Oliveira Crossetti; Eliete Regina Bertazzo Canterle; David da Motta-Marques; Maria Tereza Morais Pereira Souza Lobo; Marie-Paule Bonnet; José Rafael Cavalcanti; Jeremie Garnier; Ina de Souza Nogueira; Lúcia Ribeiro Rodrigues (Aquatic Sciences, 2025)

Antimicrobial-resistant Pseudomonas aeruginosa isolates from Brazilian environmental sources: a 13-year laboratory-based retrospective analysis - Micaela Santana Ramos; João Pedro Rueda Furlan; Lucas David Rodrigues dos Santos; Rafael da Silva Rosa; Eduardo Angelino Savazzi; Eliana Guedes Stehling (Environmental Monitoring and Assessment, 2025)

Li concentration and isotopes in kaolinite and organic of coals determined by secondary ion mass spectrometry - Jia Song; Beilei Sun; Sandra Rodrigues; Chao Liu; Zhanming Guo; David French (International Journal of Coal Geology, 2025)

Two decades of strategies, policies, and market institutions to slowdown deforestation in the Brazilian Legal Amazon - Marcos Rodrigues; David Costa Correia Silva; Josimar da Silva Freitas (Regional Environmental Change, 2025)

Purines and purinergic receptors in primary tumors of the central nervous system - Adinei Abadio Soares; Helamã Moraes dos Santos; Keyllor Nunes Domann; Natália Pratis Rocha Alves; Bernardo Ribeiro Böhm; Carolina Maliska Haack; Kailane Paula Pretto; Emily Sanini Guimarães; Guilherme Francisquini Rocha; Igor Rodrigues de Paula; Lucas Efraim de Alcântara Guimarães; Harlan Cleyton de Ávila Pessoa; et al. (Purinergic Signalling, 2025)

Genetic insights into non-additive effects in tetraploid potato breeding - Luciana Aparecida Miguel; Rafaela Pereira Carvalho; Roberto Henrique de Lima Ribeiro; Mayra Alejandra Rincón Rueda; Ivan David Briceño-Pinzón; Lucimara Cruz de Souza; Vinicius Samuel Martins; Leticia Novais Padua; José Airton Rodrigues Nunes; Pedro Crescêncio de Souza Carneiro; Mário Henrique Murad Leite Andrade; Márcio Fernando Ribeiro Resende; et al. (Euphytica, 2025)

Physico-chemical and bacteriological characteristics of groundwater in peri-urban areas of Cameroon, Central Africa: towards a new water management strategy including human-water interface - Franck Eboa; Mohammad Bello; Suzanne Ngo Boum-Nkot; Bertil Nlend; Rodrigue Ebonji; Fricelle Song; David Komba; Boris Djieugoue; Enoh Jeanot Fongoh; Andrianaivoravelona Rajaona; Pierre Ravelonandro; François Tchoumbougnang (Environmental Science and Pollution Research, 2025)

Effects of aerobic exercise and cardiorespiratory fitness on white matter free water fraction in older adults: a 1-year randomized controlled trial - Takashi Tarumi; Junyeon Won; Tsubasa Tomoto; Norman Scheel; David C. Zhu; John Ashley; Karen M. Rodrigue; Kristen M. Kennedy; Denise C. Park; Rong Zhang (GeroScience, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Toxicity of essential oils on Callosobruchus maculatus (Fabr., 1775) in grains of Vigna unguiculata - Ozael David Valério da Silva; Paulo Roberto Ramalho Silva; Leticia Rodrigues da Silva; Rodrigo de Carvalho Brito; Kamilla de Andrade Dutra; Daniela Maria do Amaral Ferraz Navarro; Douglas Rafael e Silva Barbosa; Solange Maria de França (Journal of Plant Diseases and Protection, 2025)

Multiple mechanisms of action of a triazole-derived salt against Leishmania amazonensis: Apoptosis-like death and autophagy - Andrezza Rodrigues de Souza; Luciana Maria Ribeiro Antinarelli; Ari Sergio de Oliveira Lemos; Nicolas Glanzmann; Bruno Vicente; Victor do Valle Midlej; Adolfo Firmino da Silva Neto; Rachel Rocha Pinheiro Machado; Adilson David da Silva; Elaine Soares Coimbra (Chemico-Biological Interactions, 2025)

Palaeoenvironmental reconstruction through phytolith analysis in the Casa de Pedra shell mound archaeological site, São Francisco do Sul, Santa Catarina, Brazil - David Oldack Barcelos Ferreira Machado; Heloisa Helena Gomes Coe; Dione Da Rocha Bandeira; Rosa Souza; Giliane Gessica Rasbold; Karina Ferreira Chueng; Raphaella Rodrigues Dias; Jéssica Ferreira; Celso Voos Vieira; Júlio César De Sá (Vegetation History and Archaeobotany, 2025)

Assessing the predicted impact of single amino acid substitutions in MAPK proteins for CAGI6 challenges - Paola Turina; Maria Petrosino; Carlos A. Enriquez Sandoval; Leonore Novak; Alessandra Pasquo; Emil Alexov; Muttaqi Ahmad Alladin; David B. Ascher; Giulia Babbi; Constantina Bakolitsa; Rita Casadio; Jianlin Cheng; et al. (Human Genetics, 2025)

Assessing the predicted impact of single amino acid substitutions in calmodulin for CAGI6 challenges - Paola Turina; Giuditta Dal Cortivo; Carlos A. Enriquez Sandoval; Emil Alexov; David B. Ascher; Giulia Babbi; Constantina Bakolitsa; Rita Casadio; Piero Fariselli; Lukas Folkman; Akash Kamandula; Panagiotis Katsonis; et al. (Human Genetics, 2025)

Exploring the effects of missense mutations on protein thermodynamics through structure-based approaches: findings from the CAGI6 challenges - Carlos H. M. Rodrigues; Stephanie Portelli; David B. Ascher (Human Genetics, 2025)
Missense mutations are known contributors to diverse genetic disorders, due to their subtle, single amino acid changes imparted on the resultant protein. Because of this, understanding the impact of these mutations on protein stability and function is crucial for unravelling disease mechanisms and developing targeted therapies. The Critical Assessment of Genome Interpretation (CAGI) provides a valuable platform for benchmarking state-of-the-art computational methods in predicting the impact of disease-related mutations on protein thermodynamics. Here we report the performance of our comprehensive platform of structure-based computational approaches to evaluate mutations impacting protein structure and function on 3 challenges from CAGI6: Calmodulin, MAPK1 and MAPK3. Our stability predictors have achieved correlations of up to 0.74 and AUCs of 1 when predicting changes in ΔΔ G for MAPK1 and MAPK3, respectively, and AUC of up to 0.75 in the Calmodulin challenge. Overall, our study highlights the importance of structure-based approaches in understanding the effects of missense mutations on protein thermodynamics. The results obtained from the CAGI6 challenges contribute to the ongoing efforts to enhance our understanding of disease mechanisms and facilitate the development of personalised medicine approaches.

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Measuring commitment in paws: Adaptation of the Investment Model Scale to the context of companion animals with a Portuguese sample - Tiago Rôxo Aguiar; Diniz Lopes; David L. Rodrigues (Journal of Veterinary Behavior, 2025)

Optical immunosensor panel using quantum dot-antibody conjugates for highly sensitive detection of carbohydrate antigen 19–9 (CA19-9) - Daniela Oliveira; Pedro Oliveira; Ana Xu; Eduarda Rodrigues; Susana G. Guerreiro; Rafael C. Castro; David S.M. Ribeiro; João L.M. Santos; Ana Margarida L. Piloto (Analytica Chimica Acta, 2025)

Habitat distinctness doesn't influence on the abundance and relative growth of the juveniles Atherinella brasiliensis (Quoy & Gaimard, 1824) in a subtropical estuarine ecosystem - Jorge Luiz Rodrigues Filho; Diogo Fernandes Santiago; Thiago Bif Piazza; David Valença Dantas; Victor Aguiar de Souza Penha; Joaquim Olinto Branco (Regional Studies in Marine Science, 2024)

Convergence of mcr-1 and broad-spectrum β-lactamase genes in Escherichia coli strains from the environmental sector - João Pedro Rueda Furlan; Rafael da Silva Rosa; Micaela Santana Ramos; Ralf Lopes; Lucas David Rodrigues dos Santos; Eduardo Angelino Savazzi; Eliana Guedes Stehling (Environmental Pollution, 2024)

Comparative study of non-suppurative meningoencephalitis in cattle in Southern Brazil - Francisca Maria Sousa Barbosa; Igor Ribeiro dos Santos; Bruno Albuquerque de Almeida; Franciéli Adriane Molossi; Paula Rodrigues de Almeida; Eryca Ceolin Lamego; Júlia Camargo Barth; Sara Vilar Dantas Simões; Welden Panziera; Luciana Sonne; Saulo Petinatti Pavarini; David Driemeier (Veterinary Research Communications, 2024)

Association Between Agronomic and Biomass Component Traits Using Pathway Analysis and Regression Tree Techniques in Biomass Sorghum - Gabrielle Maria Romeiro Lombardi; José Airton Rodrigues Nunes; Rafael Augusto da Costa Parrella; Michael David Batista Luaemar de Oliveira (Sugar Tech, 2024)

Metabolic effects of physical exercise on zebrafish (Danio rerio) fed a high-fat diet - Moises Silvestre de Azevedo Martins; William Franco Carneiro; Kianne Silva Monteiro; Stefania Priscilla de Souza; André Rodrigues da Cunha Barreto Vianna; Luis David Solis Murgas (Journal of Comparative Physiology B, 2024)

Resource-efficiency of cyanobacterium production on Mars: Assessment and paths forward - Tiago P. Ramalho; Vincent Baumgartner; Nils Kunst; David Rodrigues; Emma Bohuon; Basile Leroy; Guillaume Pillot; Christiane Heinicke; Sven Kerzenmacher; Marc Avila; Cyprien Verseux (Algal Research, 2024)

Long-term sustainability of the water-agriculture-energy nexus in Brazil’s MATOPIBA region: A case study using system dynamics - Minella Alves Martins; David Collste; Francisco Gilney Silva Bezerra; Marcela Aparecida Campos Neves Miranda; André Rodrigues Gonçalves; Jocilene Dantas Barros; Manoel Ferreira Cardoso; Amanda Sousa Silvino; Taís Sonetti-González; Jean Pierre Henry Balbaud Ometto; Celso von Randow; Javier Tomasella; et al. (Ambio, 2024)

Juvenile-related tolerance to papaya sticky disease (PSD): proteomic, ultrastructural, and physiological events - Silas P. Rodrigues; Eduardo de A. Soares; Tathiana F. Sá Antunes; Marlonni Maurastoni; Leidy J. Madroñero; Sabrina G. Broetto; Lucas E. C. Nunes; Brunno R. F. Verçoza; David S. Buss; Diolina M. Silva; Juliany C. F. Rodrigues; José A. Ventura; et al. (Plant Cell Reports, 2024)

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The detection of KPC-2, NDM-1, and VIM-2 carbapenemases in international clones isolated from fresh vegetables highlights an emerging food safety issue - João Pedro Rueda Furlan; Ralf Lopes; Micaela Santana Ramos; Rafael da Silva Rosa; Lucas David Rodrigues dos Santos; Eliana Guedes Stehling (International Journal of Food Microbiology, 2024)

Farm management practices and host species richness associated with higher likelihood of tuberculosis positive farms in Western Spain - Gloria Herrero-García; Rita Vaz-Rodrigues; Pilar Pozo; Patricia Barroso; David Relimpio; Jesús Nácar; Anna Grau; Olga Mínguez; Alberto García-Rodríguez; Ana Balseiro; Christian Gortázar (European Journal of Wildlife Research, 2024)
Despite enormous efforts, complete animal tuberculosis (TB) eradication has only been achieved in few regions. Epidemiological analyses are key to identify TB risk factors and set up targeted biosecurity measures. Here, we conducted an in-depth characterization of 84 extensive beef cattle farms from a high TB prevalence region in Western Spain, and assessed how farm management and wildlife presence on farms contribute to cattle TB risk. Twenty-six out of 84 variables were associated with cattle farm TB positivity. Farm management variables associated with TB positivity included older cattle, larger herd size, highly fragmented farm structure and greater connectivity between farms. TB-positive farms provided supplemental feed over a higher number of months, used calf feeders, and had higher number of waterholes. Detecting Eurasian wild boar ( Sus scrofa ), red fox ( Vulpes vulpes ), European badger ( Meles meles ), roe deer ( Capreolus capreolus ), or Egyptian mongoose ( Herpestes ichneumon ) on cattle farms was also associated with farm TB positivity. The best ordinal regression model indicated that in farms with a large herd size (> 167 animals) the odds of being positive or recurrently positive (versus negative) was 7.34 (95% CI = 2.43–23.51) times higher that of farms with small herd size. Further, for every additional host species detected in the farm premises, the odds of being TB-positive increased 56%. We conclude that both cattle management and wildlife need to be targeted for successful TB control in grazing-based farming systems.

Humane Endpoint: Example from a Murine Model of Disseminated Sporotrichosis - Vanice Rodrigues Poester; Lívia Silveira Munhoz; Mariana Rodrigues Trápaga; Bruna Muradás Esperon; David A. Stevens; Melissa Orzechowski Xavier (Current Microbiology, 2024)

Boron nutrition increase soybean seed yield and maintain the quality of germination in storage seeds - Dágila Melo Rodrigues; Cid Naudi Silva Campos; Jonas Pereira de Souza Junior; Charline Zaratin Alves; Ana Carina da Silva Cândido; Larissa Pereira Ribeiro Teodoro; Paulo Eduardo Teodoro; Paulo Carteri Coradi; Carlos Henrique Oliveira de David; Renato de Mello Prado (Acta Physiologiae Plantarum, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Proximal sensors for modeling clay mineralogy and characterization of soil textural fractions developed from contrasting parent materials - Fernanda Magno Silva; Sérgio Henrique Godinho Silva; Renata Andrade; João Augusto Coblinski; Alberto Vasconcellos Inda; Gustavo Frosi; Suane de Souza Franco Lima; Michele Duarte de Menezes; Tiago Rodrigues Tavares; Luiz Roberto Guimarães Guilherme; David C. Weindorf; Nilton Curi (CATENA, 2024)

Genetic diversity of KPC-2-producing Klebsiella pneumoniae complex from aquatic ecosystems - Rafael da Silva Rosa; João Pedro Rueda Furlan; Lucas David Rodrigues dos Santos; Micaela Santana Ramos; Eduardo Angelino Savazzi; Eliana Guedes Stehling (World Journal of Microbiology and Biotechnology, 2024)

Effects of a Mining Dam Disaster on Antimicrobial-Resistant and Metal-Tolerant Bacterial Strains Recovered from Environmental Samples - João Pedro Rueda Furlan; Micaela Santana Ramos; Lucas David Rodrigues dos Santos; Rafael da Silva Rosa; Ana Carolina Paulelli; Cecilia Cristina de Souza Rocha; Cibele Aparecida Cesila; Matheus Gallimberti; Paula Pícoli Devóz; Fernando Barbosa Júnior; Eliana Guedes Stehling (Water, Air, & Soil Pollution, 2024)

Influence of anthropogenic effects and climate variability on streamflow in a Brazilian tropical watershed - Guilherme Barbosa Reis; Demetrius David da Silva; Michel Castro Moreira; Elpídio Inácio Fernandes Filho; Micael de Souza Fraga; Roberto Avelino Cecílio; Sávio Augusto Rocha Pinheiro; Gabriel Rodrigues Arruda Pinto (Theoretical and Applied Climatology, 2024)

Aspergillosis in Critically Ill Patients with and Without COVID-19 in a Tertiary Hospital in Southern Brazil - Mariana Rodrigues Trápaga; Vanice Rodrigues Poester; Rossana Patrícia Basso; Bianca dos Santos Blan; Lívia Silveira Munhoz; Alessandro C. Pasqualotto; Talita da Fontoura Werner; Maria Letícia Figurelli; David A. Stevens; Andrea von Groll; Melissa Orzechowski Xavier (Mycopathologia, 2024)

Evaluating the bioactivity and toxicity of Siparuna guianensis Aublet (Siparunaceae) leaf extracts in zebrafish - Maria de Fátima Santos; William Franco Carneiro; Bárbara do Carmo Rodrigues Virote; Kiara Cândido Duarte da Silva; Tassia Flavia Dias Castro; Aline Pereira Coli; Luis David Solis Murgas; Marcos Ferrante; Manuel Losada Gavilanes; Elisangela Elena Nunes Carvalho (Advances in Traditional Medicine, 2024)

Dietary effect of multi-strain prebiotics and probiotics on growth, hemato-biochemical parameters, intestinal histomorphometry, and resistance to hypoxia in juvenile tambaqui (Colossoma macropomum) - Rafael José Furtado Souza; Edilson Rodrigues Matos; Aldry Lorran da Silva Souza; Paola Fabiana Fazzi-Gomes; Nuno Filipe Alves Correia de Melo; Marco Shizuo Owatari; Glauber David Almeida Palheta; Rodrigo Takata; Fabio Carneiro Sterzelecki (Veterinary Research Communications, 2024)

Effects of decreasing roughage NDF in diets with high inclusion of DDGS on performance, feeding behavior, and ruminal parameters in Nellore bulls - Gabriel Namor Issa David; Alana Maria Menezes Di Calaça; Natalia de Almeida Leite; Taniela de Souza Conrado; Izadora Mazagão Veloso; Alessandro Rodrigues Costa Filho; Felipe de Souza Galvão; Yasmin Machado Barreto; Luan de Oliveira Moura Silva; Victor Rezende Moreira Couto; Juliano José de Resende Fernandes (Livestock Science, 2024)

Nowcast flood predictions in the Amazon watershed based on the remotely sensed rainfall product PDIRnow and artificial neural networks - Herval Alves Ramos Filho; Eduardo Morgan Uliana; Uilson Ricardo Venâncio Aires; Ibraim Fantin da Cruz; Luana Lisboa; Demetrius David da Silva; Marcelo Ribeiro Viola; Victor Braga Rodrigues Duarte (Environmental Monitoring and Assessment, 2024)

Exploring the effects of eugenol, menthol, and lidocaine as anesthetics on zebrafish glucose homeostasis - Gabriela Maressa Machado Baesso; Amanda Vitória Venâncio; Lívia Costa Varela Barca; Pepita Fernanda Peppi; Caique Aparecido Faria; João Pedro Cosmo Machado; Luiz David Solis Murgas; Álvaro José de Almeida Bicudo; Eduardo Maurício Mendes de Lima; André Rodrigues da Cunha Barreto-Vianna (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

PPARγ partial agonist LPSF/GQ-16 prevents dermal and pulmonary fibrosis in HOCl-induced systemic sclerosis (SSc) and modulates cytokine production in PBMC of SSc patients - Anderson Rodrigues de Almeida; Andréa Tavares Dantas; Maria Eduarda de Oliveira Gonçalves; Charlotte Chêne; Mohamed Jeljeli; Sandrine Chouzenoux; Marine Thomas; Eudes Gustavo Constantino Cunha; Lilian David de Azevedo Valadares; João Victor de Melo Gomes; Simão Kalebe Silva de Paula; Marina Galdino da Rocha Pitta; et al. (Inflammopharmacology, 2024)

Protective Association of APOC1/rs4420638 with Risk of Obesity: A case-control Study in Portuguese Children - Licínio Manco; David Albuquerque; Daniela Rodrigues; Aristides M. Machado-Rodrigues; Cristina Padez (Biochemical Genetics, 2024)
The association of the rs4420638 polymorphism, near the APOC1 gene, was examined with the risk of obesity among Portuguese children. A sample of 446 Portuguese individuals (231 boys and 215 girls) of European descent, aged 3.2 to 13.7 years old (mean age: 7.98 years), were selected to conduct a case-control study. Body mass index (BMI), BMI Z-scores, and waist circumference were calculated. Genotyping was performed by real time PCR using a pre-designed TaqMan probe. Logistic regression and the nonparametric Mann-Whitney test were used to test the associations. The association results revealed a significant protective effect from the minor G-allele of SNP rs4420638 against obesity, with an odds ratio (OR) of 0.619 (95% CI 0.421–0.913; p = 0.0155) in the additive model, and OR of 0.587 (95% CI 0.383-0.9; p = 0.0145) in the dominant model. Moreover, comparing genotype groups (AA vs. AG + GG), significantly lower values ( p APOE / APOC1 candidate-region association with the risk of obesity. This was the first study to describe the protective association of the rs4420638 minor G-allele against obesity in childhood exclusively.

Species distribution modelling in the Southwestern Atlantic Ocean: A systematic review and trends - Lucas dos Santos Rodrigues; Nicholas Winterle Daudt; Luis Gustavo Cardoso; Paul Gerhard Kinas; David Conesa; Maria Grazia Pennino (Ecological Modelling, 2023)

Multidrug-resistant Shiga toxin-producing Escherichia coli and hybrid pathogenic strains of bovine origin - João Pedro Rueda Furlan; Micaela Santana Ramos; Lucas David Rodrigues dos Santos; Rafael da Silva Rosa; Eliana Guedes Stehling (Veterinary Research Communications, 2023)

3D topological analysis in deformation bands: Insights for structural characterization and impact on permeability - Raquel Bezerra Rodrigues de Melo Freitas; Francisco Cézar Costa Nogueira; David Lino Vasconcelos; Gabriel de Brito Honório; Matheus Amador Nicchio; Rômulo de Campos Stohler; Jorge André Braz de Souza (Journal of Structural Geology, 2023)

An iota-carrageenan isolated from marine alga Agardhiella ramosissima negatively modulates the inflammatory response in arthritis conditions - Lucas Henrique Marques Rodrigues; Francisco Fábio Bezerra de Oliveira; Francisco Felipe Bezerra; Samara Rodrigues Bonfim Damasceno Oliveira; Rudy Diavila Bingana; Luana David do Carmo; Márcia Rúbia Silva Melo; Luciano de Sousa Chaves; André Luiz dos Reis Barbosa; Jand-Venes Rolim Medeiros; Pedro Marcos Gomes Soares; Paulo Antônio de Souza Mourão; et al. (Bioactive Carbohydrates and Dietary Fibre, 2023)

Utilization of Rosuvastatin and Endogenous Biomarkers in Evaluating the Impact of Ritlecitinib on BCRP, OATP1B1, and OAT3 Transporter Activity - Yeamin Huh; Anna Plotka; Hua Wei; Julia Kaplan; Nancy Raha; Justin Towner; Vivek S. Purohit; Martin E. Dowty; Robert Wolk; Manoli Vourvahis; Amanda King-Ahmad; Sumathy Mathialagan; et al. (Pharmaceutical Research, 2023)
Purpose Ritlecitinib, an inhibitor of Janus kinase 3 and tyrosine kinase expressed in hepatocellular carcinoma family kinases, is in development for inflammatory diseases. This study assessed the impact of ritlecitinib on drug transporters using a probe drug and endogenous biomarkers. Methods In vitro transporter-mediated substrate uptake and inhibition by ritlecitinib and its major metabolite were evaluated. Subsequently, a clinical drug interaction study was conducted in 12 healthy adult participants to assess the effect of ritlecitinib on pharmacokinetics of rosuvastatin, a substrate of breast cancer resistance protein (BCRP), organic anion transporting polypeptide 1B1 (OATP1B1), and organic anion transporter 3 (OAT3). Plasma concentrations of coproporphyrin I (CP-I) and pyridoxic acid (PDA) were assessed as endogenous biomarkers for OATP1B1 and OAT1/3 function, respectively. Results In vitro studies suggested that ritlecitinib can potentially inhibit BCRP, OATP1B1 and OAT1/3 based on regulatory cutoffs. In the subsequent clinical study, coadministration of ritlecitinib decreased rosuvastatin plasma exposure area under the curve from time 0 to infinity (AUC inf ) by ~ 13% and maximum concentration (C max ) by ~ 27% relative to rosuvastatin administered alone. Renal clearance was comparable in the absence and presence of ritlecitinib coadministration. PK parameters of AUC inf and C max for CP-I and PDA were also similar regardless of ritlecitinib coadministration. Conclusion Ritlecitinib does not inhibit BCRP, OATP1B1, and OAT3 and is unlikely to cause a clinically relevant interaction through these transporters. Furthermore, our findings add to the body of evidence supporting the utility of CP-I and PDA as endogenous biomarkers for assessment of OATP1B1 and OAT1/3 transporter activity.

Genomic features of an extensively drug-resistant and NDM-1–positive Klebsiella pneumoniae ST340 isolated from river water - João Pedro Rueda Furlan; Rafael da Silva Rosa; Micaela Santana Ramos; Lucas David Rodrigues dos Santos; Eduardo Angelino Savazzi; Eliana Guedes Stehling (Environmental Science and Pollution Research, 2023)

Composition and diversity of fish assemblages along a shallow beach of a neotropical coastal lagoon - Catarina de C.A. Frischknecht; David V. Dantas; Jorge L. Rodrigues-Filho; Eduardo Gentil (Regional Studies in Marine Science, 2023)

Non-invasive methods to quantify the carcass parameters of sheep: Interaction between thermal environment and residual feed intake - Gabriel Ravi Gama Fontes; Glayciane Costa Gois; Rafael Torres de Souza Rodrigues; David Ramos da Rocha; Tiago Santos Silva; Joanigo Fernando Simão; Nataline Silva Araújo; Silvia Helena Nogueira Turco; Flávio Barbosa Matias; José Gledyson da Silva; Bernardo José Marques Ferreira; Daniel Ribeiro Menezes; et al. (Journal of Thermal Biology, 2023)

Forecasting of daily streamflows downstream from reservoirs with streamflow regularization using machine learning methods - Tarcila Neves Generoso; Demetrius David da Silva; Ricardo Santos Silva Amorim; Lineu Neiva Rodrigues; Daniel Althoff; Erli Pinto dos Santos (Journal of South American Earth Sciences, 2023)

Levels of leucaena hay associated with cactus pear in diets for crossbred steers - Weudes Rodrigues Andrade; Gabriel Santos Souza David; Fábio Andrade Teixeira; José Augusto Gomes Azevêdo; Ariomar Rodrigues dos Santos; Messias de Sousa Nogueira; Aureliano Jose Vieira Pires (Tropical Animal Health and Production, 2023)

Daily responses of the planktonic food web to environmental dynamics in the vegetated littoral zone of a large shallow lake - Luana Morais da Rosa; Luciana de Souza Cardoso; Mônica Hessel Silveira; Luciane Oliveira Crossetti; Eliete Regina Bertazzo Canterle; José Rafael Cavalcanti; David da Motta-Marques; Lúcia Ribeiro Rodrigues (Limnologica, 2023)

Analysis of the criteria for improving biogas production: focus on anaerobic digestion - Oumoul-Kairou Karidio Daouda Idrissa; David Tsuanyo; Rodrigue Adjoumani Kouakou; Yacouba Konaté; Boukary Sawadogo; Kouassi Benjamin Yao (Environment, Development and Sustainability, 2023)

Trend analysis and identification of possible periods of change in the occurrence of extreme streamflow events in a tropical basin - Carla Larissa Fonseca da Silva; Demetrius David da Silva; Michel Castro Moreira; Jackson Martins Rodrigues; Igor Steven de Sousa Rocha; Rafael Petruceli Coelho Lima; Arthur Telles Calegario (Journal of South American Earth Sciences, 2023)

Genetic plurality of blaKPC-2-harboring plasmids in high-risk clones of Klebsiella pneumoniae of environmental origin - João Pedro Rueda Furlan; Rafael da Silva Rosa; Micaela Santana Ramos; Lucas David Rodrigues dos Santos; Ralf Lopes; Eduardo Angelino Savazzi; Eliana Guedes Stehling (Science of The Total Environment, 2023)

Detailed characterization of iron-rich tailings after the Fundão dam failure, Brazil, with inclusion of proximal sensors data, as a secure basis for environmental and agricultural restoration - Rafaella T. Silva de Sá; Marcelo Tesser Antunes Prianti; Renata Andrade; Aline Oliveira Silva; Éder Rodrigues Batista; Jessé Valentim dos Santos; Fernanda Magno Silva; Marco Aurélio Carbone Carneiro; Luiz Roberto Guimarães Guilherme; Somsubhra Chakraborty; David C. Weindorf; Nilton Curi; et al. (Environmental Research, 2023)

Sex and the Estrous-Cycle Phase Influence the Expression of G Protein-Coupled Estrogen Receptor 1 (GPER) in Schizophrenia: Translational Evidence for a New Target - Francisco Eliclécio Rodrigues da Silva; Rafaela Carneiro Cordeiro; Camila N. de Carvalho Lima; Pablo Leal Cardozo; Germana Silva Vasconcelos; Aline Santos Monte; Lia Lira Olivier Sanders; Silvânia Maria Mendes Vasconcelos; David Freitas de Lucena; Breno Fiuza Cruz; Rodrigo Nicolato; Mary V. Seeman; et al. (Molecular Neurobiology, 2023)

Inclusion of calcium oxide in sugarcane silage under different particle sizes on performance of dairy cows - Weudes Rodrigues Andrade; Thiara Jacira Vicuna Mendes Oliveir de Paula Machado; Gabriel Santos Souza David; Aureliano José Vieira Pires; Gleidson Giordano Pinto de Carvalho; Susi Cristina dos Santos Guimarães Martins; Luiz Carlos Oliveira de Sousa (Tropical Animal Health and Production, 2023)

Correction to: Characterization of Portuguese sown rainfed grasslands using remote sensing and machine learning - Tiago G. Morais; Marjan Jongen; Camila Tufik; Nuno R. Rodrigues; Ivo Gama; David Fangueiro; João Serrano; Susana Vieira; Tiago Domingos; Ricardo F. M. Teixeira (Precision Agriculture, 2023)

Patterns of antimicrobial resistance and metal tolerance in environmental Pseudomonas aeruginosa isolates and the genomic characterization of the rare O6/ST900 clone - Micaela Santana Ramos; João Pedro Rueda Furlan; Lucas David Rodrigues dos Santos; Rafael da Silva Rosa; Eduardo Angelino Savazzi; Eliana Guedes Stehling (Environmental Monitoring and Assessment, 2023)

Atmospheric patterns favourable to storm surge events on the coast of São Paulo State, Brazil - Marcely Sondermann; Sin Chan Chou; Celia Regina de Gouveia Souza; Judith Rodrigues; Jean David Caprace (Natural Hazards, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Machine learning-based modeling of surface sediment concentration in Doce river basin - Uilson Ricardo Venâncio Aires; Demetrius David da Silva; Elpídio Inácio Fernandes Filho; Lineu Neiva Rodrigues; Eduardo Morgan Uliana; Ricardo Santos Silva Amorim; Celso Bandeira de Melo Ribeiro; Jasmine Alves Campos (Journal of Hydrology, 2023)

Future weather generator for building performance research: An open-source morphing tool and an application - Eugénio Rodrigues; Marco S. Fernandes; David Carvalho (Building and Environment, 2023)

Impact of climate changes in the suitable areas for Coffea arabica L. production in Mozambique: Agroforestry as an alternative management system to strengthen crop sustainability - Crimildo T. Cassamo; David Draper; Maria M. Romeiras; Isabel Marques; Rogério Chiulele; Marisa Rodrigues; Marc Stalmans; Fábio L. Partelli; Ana Ribeiro-Barros; José C. Ramalho (Agriculture, Ecosystems & Environment, 2023)

The Cretaceous (early Albian to early Campanian) biostratigraphy and palaeotemperature reconstruction of the eastern Tethys: Calcareous nannofossil evidence from southern Tibet, China - Yi Zhang; Xuan Liu; David K. Watkins; Mauro Daniel Rodrigues Bruno; Hanwei Yao; Kaibo Han; Huifang Guo; Shuaipeng Zhu; Xi Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Characterization of portuguese sown rainfed grasslands using remote sensing and machine learning - Tiago G. Morais; Marjan Jongen; Camila Tufik; Nuno R. Rodrigues; Ivo Gama; David Fangueiro; João Serrano; Susana Vieira; Tiago Domingos; Ricardo F.M. Teixeira (Precision Agriculture, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Modelling the distribution of marine fishery resources: Where are we? - Lucas dos Santos Rodrigues; Maria Grazia Pennino; David Conesa; Eidi Kikuchi; Paul Gerhard Kinas; Fabiana Gonçalves Barbosa; Luís Gustavo Cardoso (Fish and Fisheries, 2023)
Ecological niche models (ENMs) and species distribution models (SDMs) have been widely applied to various studies relevant to biogeography, conservation biology, and ecology. These modelling techniques seek to develop spatial maps for projecting, among others past, current, and future species distributions. Born in the field of terrestrial ecology, only in recent years have these models been applied to marine environmental issues, especially to improve the forecasting of the distribution of occurrences and capturing of fishery resources. This study aimed to present through bibliometric analysis the characteristics of articles related to the use of ENMs and SDMs in marine fishery resources considering three main points: (1) state of the art: number of articles over the years, journals, countries, collaborations, and focus of research; (2) characteristics linked to fishery resources: marine biogeographic realms, taxonomic groups, life phases, oceanographic zones, and behaviours; (3) characteristics linked to methods: type of method, type of biological and, environmental data. We provide a list of 378 articles (derived from 930 screened ones), the results, and a discussion of our findings, which represent a baseline for the current status (strengths, limits, and gaps) of the interface between ENMs/SDMs and fishery resources.

Use of oral fluid samples for the investigation of outbreaks of human parvovirus B19 infection - Daiana Lima Almada; Arthur Daniel Rocha Alves; Luciane Almeida Amado Leon; Débora Familiar Rodrigues Macedo; Solange Artimos de Oliveira; Marilda Mendonça Siqueira; David Brown; Rita de Cássia Nasser Cubel Garcia (Brazilian Journal of Microbiology, 2022)

SARS-CoV-2 in Human Sewage and River Water from a Remote and Vulnerable Area as a Surveillance Tool in Brazil - Gislaine Fongaro; Paula Rogovski; Beatriz Pereira Savi; Rafael Dorighello Cadamuro; Juliana Virgínia Faria Pereira; Iago Hashimoto Sant Anna; Ivan Henrique Rodrigues; Doris Sobral Marques Souza; Edgard Gregory Torres Saravia; David Rodríguez-Lázaro; Maria Célia da Silva Lanna (Food and Environmental Virology, 2022)

Anti-Aspergillus fumigatus IgG in patients with bronchiectasis and its relationship with clinical outcome - Mariana Rodrigues Trápaga; Vanice Rodrigues Poester; Karine Ortiz Sanchotene; Aryse Martins Melo; Jéssica Louise Benelli; Rossana Patricia Basso; Gabriel Baracy Klafke; Daniela Fernandes Ramos; Cristina Veríssimo; Raquel Sabino; David A. Stevens; Melissa Orzechowski Xavier (Archives of Microbiology, 2022)

A predictive model of wheat grain yield based on canopy reflectance indices and theoretical definition of yield potential - João Paulo Pennacchi; Nicolas Virlet; João Paulo Rodrigues Alves Delfino Barbosa; Martin A. J. Parry; David Feuerhelm; Malcolm Hawkesford; Elizabete Carmo-Silva (Theoretical and Experimental Plant Physiology, 2022)

Anti-inflammatory and anti-necrotic effects of lectins from Canavalia ensiformis and Canavalia brasiliensis in experimental acute pancreatitis - Samara Rodrigues Bonfim Damasceno Oliveira; Álvaro Xavier Franco; Marielle Pires Quaresma; Cecília Mendes Morais de Carvalho; Fabrícia da Cunha Jácome Marques; Patrícia da Silva Pantoja; Vanessa Azevedo Mendonça; Vinicius José da Silva Osterne; Jorge Luis Almeida Correia; Ana Maria Sampaio Assreuy; Marcellus Henrique Loiola Pontes de Souza; Kyria Santiago do Nascimento; et al. (Glycoconjugate Journal, 2022)

Kinetic, thermodynamic and physical-chemical study of the removal of copper from cachaça using coconut fibers - Richard Bispo Barbosa; Zuy Maria Magriotis; Ana Paula Andrade Gândara; Wilder Douglas Santiago; Gabriela Fontes Alvarenga; Rafaela Magalhães Brandão; Renan Elan da Silva Oliveira; Alex Rodrigues Silva Caetano; David Lee Nelson; Maria das Graças Cardoso (Food Additives & Contaminants: Part A, 2022)

Analysis of Flow Behavior as Influenced by Reservoir with Flow Regularization - Tarcila Neves Generoso; Demetrius David da Silva; Lineu Neiva Rodrigues; Ricardo Santos Silva Amorim; Laura Thebit de Almeida (Water Resources Management, 2022)

Methodology for Estimating Streamflow by Water Balance and Rating Curve Methods Based on Logistic Regression - Tarcila Neves Generoso; Demetrius David da Silva; Ricardo Santos Silva Amorim; Lineu Neiva Rodrigues; Erli Pinto dos Santos (Water Resources Management, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Pseudomonas phaseolicola preferentially modulates genes encoding leucine-rich repeat and malectin domains in the bean landrace G2333 - Paula Rodrigues Oblessuc; David F. Bridges; Maeli Melotto (Planta, 2022)
Main conclusion Candidate resistance genes encoding malectin-like and LRR domains mapped to halo blight resistance loci throughout the common bean genome are co-expressed to fight a range of Pph races. Abstract Common bean ( Phaseolus vulgaris L.) is an important crop both as a source of protein and other nutrients for human nutrition and as a nitrogen fixer that benefits sustainable agriculture. This crop is affected by halo blight disease, caused by the bacterium Pseudomonas syringae pv. phaseolicola ( Pph ), which can lead to 45% yield losses. Common bean resistance to Pph is conferred by six loci ( Pse-1 to Pse-6 ) and minor-effect quantitative trait loci (QTLs); however, information is lacking on the molecular mechanisms implicated in this resistance. Here, we describe an in-depth RNA-sequencing (RNA-seq) analysis of the tolerant G2333 bean line in response to the Pph strain NPS3121. We identified 275 upregulated and 357 downregulated common bean genes in response to Pph infection. These differentially expressed genes were mapped to all 11 chromosomes of P. vulgaris . The upregulated genes were primarily components of plant immune responses and negative regulation of photosynthesis, with enrichment for leucine-rich repeat (LRRs) and/or malectin-like carbohydrate-binding domains. Interestingly, LRRs and malectin genes mapped to the same location as previously identified Pph resistance loci or QTLs. For instance, the major loci Pse-6 /HB4.2 involved in broad-resistance to many Pph races co-located with induced LRR-encoding genes on Pv04. These findings indicate a coordinated modulation of genes involved in pathogen perception and signal transduction. In addition, the results further support these LRR/malectin loci as resistance genes in response to halo blight. Thus, these genes are potential targets for future genetic manipulation, enabling the introduction of resistance to Pph into elite cultivars of common bean.

Fungal Bloodstream Co-infection by Trichosporon asahii in a COVID-19 Critical Patient: Case Report and Literature Review - Jéssica Louise Benelli; Rossana Patrícia Basso; Talita Werner Grafulha; Vanice Rodrigues Poester; Lívia Silveira Munhoz; Katheryne Benine Martins; Heruza Einsfeld Zogbi; Andrea Von Groll; Cecília Bittencourt Severo; David A. Stevens; Melissa Orzechowski Xavier (Mycopathologia, 2022)

Asynchrony, density dependence, and persistence in an amphibian - Freya E. Rowland; Elizabeth S. Schyling; L. Kealoha Freidenburg; Mark C. Urban; Jonathan L. Richardson; A. Z. Andis Arietta; Susan B. Rodrigues; Adriana D. Rubinstein; Michael F. Benard; David K. Skelly (Ecology, 2022)
Understanding drivers of metapopulation dynamics remains a critical challenge for ecology and conservation. In particular, the degree of synchrony in metapopulation dynamics determines how resilient a metapopulation is to a widespread disturbance. In this study, we used 21 years of egg mass count data across 64 nonpermanent freshwater ponds in Connecticut, USA to evaluate patterns of abundance and growth and to assess regional as well as local factors in shaping the population dynamics of wood frogs ( Rana sylvatica = Lithobates sylvaticus ). In particular, we asked whether a species known to undergo metapopulation dynamics exhibited spatial synchrony in abundances. With the exception of a single year when breeding took place during severe drought conditions, our analyses revealed no evidence of synchrony despite close proximity (mean minimum distance

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Pyrolysis of Coconut Inflorescence Wastes: Production, Effects of Parameters, Characterization and Optimization of Phenolic-Rich Bio-Oil - Rodrigo Oliveira Farias; Pollyanna Vanessa Santos Lins; Rafaela Gabriel; Alson David Rodrigues Silva; Lívia Luísa Melo Carvalho; Lucas Meili; Allan Almeida Albuquerque; Sandra Helena Vieira Carvalho; João Inácio Soletti; Mozart Daltro Bispo (International Journal of Environmental Research, 2022)

Projected impacts of 1.5 and 2°C global warming on temperature and precipitation patterns in South America - Roger Rodrigues Torres; Rafael Bitencourt Benassi; Fabrina Bolzan Martins; David Montenegro Lapola (International Journal of Climatology, 2022)
Even if the thresholds set out in the Paris Agreement are reached, several impacts on the climate system are still inevitable, generating new vulnerabilities and amplifying those that already exist. In this sense, the objective of this work was to analyse the impact of a global warming of 1.5 and 2°C in the regional climatological patterns of the near‐surface air temperature and precipitation over South America, locating the most affected regions and briefly discussing the possible impacts to be faced on biodiversity and agriculture. The simulations and projections of 26 General Circulation Models (GCMs) from the Coupled Model Intercomparison Project Phase 5 were used, forced in four different Representative Concentration Pathways (RCPs) scenarios. Projections for 1.5 or 2°C global warming indicate a local increase even higher, of at least +0.5°C, in almost the entire South American continent. Regarding precipitation, a similar pattern was also found between the two thresholds of global warming. GCMs project an increase of about 100 mm year −1 in the southern region of Brazil and in the northern portion of the Brazilian Northeast, in northern Argentina, Uruguay, and parts of Peru, Ecuador, Colombia and Venezuela; while the areas between the south of Chile and Argentina and the extreme north of South America show reductions of up to 150 mm year −1 . In addition, both the temperature and precipitation patterns were practically similar between the four analysed RCPs scenarios. The results presented in this study indicate that even if the Paris Agreement is very successful, South America will still suffer several impacts and will need to take effective adaptation measures in the short term. This may have pervasive implications for the biodiversity and genetic resource base of the subcontinent, as well as may impair agricultural productivity or incur into considerable adaptation costs for the sector.

Novel Lethal Clostridial Infection in Florida Manatees (Trichechus manatus latirostris): Cause of the 2013 Unusual Mortality Event in the Indian River Lagoon - Jan H. Landsberg; Maki Tabuchi; David S. Rotstein; Kuttichantran Subramaniam; Thais C. S. Rodrigues; Thomas B. Waltzek; Nicole I. Stacy; Patrick W. Wilson; Yasunari Kiryu; Francisco A. Uzal; Martine de Wit (Frontiers in Marine Science, 2022)
The Indian River Lagoon (IRL) on Florida’s east coast is a biologically diverse estuary and an important habitat to the threatened Florida manatee ( Trichechus manatus latirostris ). An unusual mortality event (UME) was declared by the Working Group on Marine Mammal Unusual Mortality Events in 2013 after a marked increase in manatee deaths in the IRL of an unknown cause. This UME followed a dramatic reduction of seagrass coverage in the IRL due to chronic non-toxic phytoplankton blooms, with a resultant ecosystem shift to mixed macroalgal dominance. At least 199 manatee deaths fitting the UME case definition were documented in and adjacent to the IRL during 2012–2019; mortality was highest in 2013, when 111 of these deaths were documented. The case definition included carcasses in good nutritional condition, with multiorgan congestion or wet lungs consistent with drowning without trauma. The gastrointestinal compartments of manatee carcasses were filled with diverse macroalga species, and the contents were notably more fluid than usual. Gross intestinal findings included blebbing to segmental thickening of the wall. Microscopic lesions were primarily intestinal, including necrosis, edema, hemorrhage, mucosa-associated lymphoid changes, and inflammation, sometimes associated with Gram-positive bacterial rods. A multidisciplinary approach of environmental and carcass sampling found no causative evidence through tests for micro- and macroalgal biotoxins, trace metals, general toxin screening, or vitreum biochemistry. Microbiological, cytological, immunohistochemical, and molecular analyses of Clostridiales from intestinal samples identified Clostridioides difficile toxin A, toxins A/B and toxin A gene; Paeniclostridium sordellii lethal gene (and other potential virulence factors from a sequenced strain); and Clostridium perfringens alpha and epsilon toxin genes. The results from this 8 year-long investigation are indicative that the cause of death in this manatee UME was associated with clostridial infection, initiated by a shift to a predominantly macroalgal diet.

Climate and management effects on the herbaceous layer productivity of a cork oak woodland - M. C. Bicho; A. C. Correia; A. R. Rodrigues; J. Soares David; F. Costa-e-Silva (Agroforestry Systems, 2022)

Antitumor effect of Cymbopogon densiflorus (Linneu) essential oil in bladder cancer cells - Gizele Lucia da Costa Pereira; Tamires Cunha Almeida; Janaina Brandão Seibert; Tatiane Roquete Amparo; Rodrigo Dian de Oliveira Aguiar Soares; Ivanildes Vasconcelos Rodrigues; Gustavo Henrique Bianco de Souza; Orlando David Henrique dos Santos; Glenda Nicioli da Silva (Natural Product Research, 2021)

Insulin and glucose regulation at rest and during flight in a Neotropical nectar-feeding bat - David Leonardo Justinico Castro; Renata Maria P. Freitas; Stella Bicalho Silva; Fabiana Cristina Silveira Alves de Melo; Mariaurea M. Sarandy; Esteban Giraldo Ospina; Sirlene Rodrigues Sartori; Reggiani Vilela Gonçalves; Mariella Bontempo Freitas (Mammalian Biology, 2021)

In vitro anti-Cryptococcus activity of diphenyl diselenide alone and in combination with amphotericin B and fluconazole - Jéssica Louise Benelli; Vanice Rodrigues Poester; Lívia Silveira Munhoz; Gabriel Baracy Klafke; David A. Stevens; Melissa Orzechowski Xavier (Brazilian Journal of Microbiology, 2021)

Quorum sensing disruption regulates hydrolytic enzyme and biofilm production in estuarine bacteria - Marion Urvoy; Raphaël Lami; Catherine Dreanno; David Daudé; Alice M. S. Rodrigues; Michèle Gourmelon; Stéphane L'Helguen; Claire Labry (Environmental Microbiology, 2021)
Summary Biofilms of heterotrophic bacteria cover organic matter aggregates and constitute hotspots of mineralization, primarily acting through extracellular hydrolytic enzyme production. Nevertheless, regulation of both biofilm and hydrolytic enzyme synthesis remains poorly investigated, especially in estuarine ecosystems. In this study, various bioassays, mass spectrometry and genomics approaches were combined to test the possible involvement of quorum sensing (QS) in these mechanisms. QS is a bacterial cell–cell communication system that relies notably on the emission of N ‐acylhomoserine lactones (AHLs). In our estuarine bacterial collection, we found that 28 strains (9%), mainly Vibrio , Pseudomonas and Acinetobacter isolates, produced at least 14 different types of AHLs encoded by various luxI genes. We then inhibited the AHL QS circuits of those 28 strains using a broad‐spectrum lactonase preparation and tested whether biofilm production as well as β‐glucosidase and leucine‐aminopeptidase activities were impacted. Interestingly, we recorded contrasted responses, as biofilm production, dissolved and cell‐bound β‐glucosidase and leucine‐aminopeptidase activities significantly increased in 4%–68% of strains but decreased in 0%–21% of strains. These findings highlight the key role of AHL‐based QS in estuarine bacterial physiology and ultimately on biogeochemical cycles. They also point out the complexity of QS regulations within natural microbial assemblages.

Evidence-Based Guidelines for Drug Interaction Studies: Model-Informed Time Course of Intestinal and Hepatic CYP3A4 Inhibition by Clarithromycin - Asha J Kapetas; Ahmad Y Abuhelwa; Michael J Sorich; Ross A McKinnon; A David Rodrigues; Andrew Rowland; Ashley M Hopkins (The AAPS Journal, 2021)

Light- and nutrient-related relationships in mixed plantations of Eucalyptus and a high diversity of native tree species - Nino Tavares Amazonas; David I. Forrester; Carina Camargo Silva; Danilo Roberti Alves de Almeida; Rafael Silva Oliveira; Ricardo Ribeiro Rodrigues; Pedro H. S. Brancalion (New Forests, 2021)

Swine polioencephalomyelitis in Brazil: identification of Teschovirus A, Sapelovirus A, and Enterovirus G in a farm from Southern Brazil - Márcia Elisa Hammerschmitt; Paula Rodrigues de Almeida; Bianca Santana de Cecco; Marina Paula Lorenzett; Claiton Ismael Schwertz; Raquel Aparecida Sales da Cruz; Rafaela Albuquerque Caprioli; Daniela Teresa Schuh; Meriane Demoliner; Ana Karolina Antunes Eisen; Fernando Rosado Spilki; Saulo Petinatti Pavarini; et al. (Brazilian Journal of Microbiology, 2021)

Diphenyl diselenide alone and in combination with itraconazole against Sporothrix schenckii s.str. and Sporothrix globosa - Vanice Rodrigues Poester; Lívia Silveira Munhoz; Cristina Wayne Nogueira; Gilson Rogério Zeni; David A. Stevens; Melissa Orzechowski Xavier (Brazilian Journal of Microbiology, 2021)

Meteorological drivers and ENSO influence on phytoplankton biomass dynamics in a shallow subtropical lake - Andressa da Rosa Wieliczko; Luciane Oliveira Crossetti; J. Rafael Cavalcanti; Mônica Silveira Hessel; David da Motta-Marques; Lucia Ribeiro Rodrigues (Environmental Monitoring and Assessment, 2021)

Synergism of Nikkomycin Z in Combination with Diphenyl Diselenide Against Sporothrix spp. - Vanice Rodrigues Poester; Lívia Silveira Munhoz; Jéssica Louise Benelli; Gabriel Baracy Klafke; Cristina Wayne Nogueira; Gilson Rogério Zeni; David A. Stevens; David Larwood; Melissa Orzechowski Xavier (Current Microbiology, 2021)

Urban adaptation index: assessing cities readiness to deal with climate change - Eduardo Alves Neder; Fabiano de Araújo Moreira; Michele Dalla Fontana; Roger Rodrigues Torres; David Montenegro Lapola; Maria da Penha Costa Vasconcellos; Ana Maria Barbieri Bedran-Martins; Arlindo Philippi Junior; Maria Carmen Lemos; Gabriela Marques Di Giulio (Climatic Change, 2021)

(3,3’-Methylene)bis-2-hydroxy-1,4-naphthoquinones induce cytotoxicity against DU145 and PC3 cancer cells by inhibiting cell viability and promoting cell cycle arrest - Paula Priscilla de Freitas; Ruan Carlos Busquet Ribeiro; Isabella dos Santos Guimarães; Caroline S. Moreira; David R. Rocha; Fernando de Carvalho da Silva; Vitor Francisco Ferreira; Etel Rodrigues Pereira Gimba (Molecular Biology Reports, 2021)

North Atlantic Basin-Scale Multi-Criteria Assessment Database to Inform Effective Management and Protection of Vulnerable Marine Ecosystems - Telmo Morato; Christopher K. Pham; Laurence Fauconnet; Gerald H. Taranto; Giovanni Chimienti; Erik Cordes; Carlos Dominguez-Carrió; Pablo Durán Muñoz; Hronn Egilsdottir; José-Manuel González-Irusta; Anthony Grehan; Dierk Hebbeln; et al. (Frontiers in Marine Science, 2021)

Methodology for Allocation of Best Management Practices Integrated with the Urban Landscape - Ana Luiza Melo Rodrigues; Demetrius David da Silva; Frederico Carlos Martins de Menezes Filho (Water Resources Management, 2021)

COVID-19-Associated Histoplasmosis in an AIDS Patient - Rossana Patricia Basso; Vanice Rodrigues Poester; Jéssica Louise Benelli; David A. Stevens; Heruza Einsfeld Zogbi; Izadora Clezar da S. Vasconcellos; Alessandro Comarú Pasqualotto; Melissa Orzechowski Xavier (Mycopathologia, 2021)

Impact of climate change on groundwater recharge in a Brazilian Savannah watershed - Arnaldo José Cambraia Neto; Lineu Neiva Rodrigues; Demetrius David da Silva; Daniel Althoff (Theoretical and Applied Climatology, 2021)

Application of Model Informed Precision Dosing to Address the Impact of Pregnancy Stage and CYP2D6 Phenotype on Foetal Morphine Exposure - Sarah Badaoui; Ashley M. Hopkins; A David Rodrigues; John O. Miners; Michael J. Sorich; Andrew Rowland (The AAPS Journal, 2021)

Influence of changes in land use and land cover and rainfall on the streamflow regime of a watershed located in the transitioning region of the Brazilian Biomes Atlantic Forest and Cerrado - Fernanda Laurinda Valadares Ferreira; Lineu Neiva Rodrigues; Demetrius David da Silva (Environmental Monitoring and Assessment, 2021)

Selection underlies phenotypic divergence in the insular Azores woodpigeon - Pedro Andrade; Daniele Cataldo; Rémi Fontaine; Tiago M. Rodrigues; João Queirós; Verónica Neves; Amélia Fonseca; Miguel Carneiro; David Gonçalves (Zoologica Scripta, 2021)
The study of phenotypic evolution in island birds following colonization is a classic topic in island biogeography. However, few studies explicitly test for the role of selection in shaping trait evolution in these taxa. Here, we studied the Azores woodpigeon ( Columba palumbus azorica ) to investigate differences between island and mainland populations, between females and males, and interactions between geographical origin and sex, by using spectrophotometry to quantify plumage colour and linear measurements to examine external and skeletal morphology. We further tested if selection explains the observed patterns by comparing phenotypic differentiation to genome‐wide neutral differentiation. Our findings are consistent with several predictions of morphological evolution in island birds, namely differences in bill, flight and leg morphology and coloration differences between island and mainland birds. Interestingly, some plumage and morphological traits that differ between females and males respond differently according to geographical origin. Sexual dimorphism in colour saturation is more pronounced in the mainland, but this is driven by selection on female plumage coloration. Differences in flight morphology between females and males are also more pronounced in the mainland, possibly to accommodate contrasting pressures between migration and flight displays. Overall, our results suggest that phenotypic differentiation between mainland and island populations leading to divergent sexual dimorphism patterns can arise from selection acting on both females and males on traits that are likely under the influence of natural and sexual selection.

Combined Soil and Foliar Nitrogen Fertilization Effects on Rainfed Almond Tree Performance - Maria C. Morais; Alfredo Aires; David Barreales; M. Ângelo Rodrigues; António C. Ribeiro; Berta Gonçalves; Ana P. Silva (Journal of Soil Science and Plant Nutrition, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

High Level of Resistance to Antimicrobials and Heavy Metals in Multidrug-Resistant Pseudomonas sp. Isolated from Water Sources - Micaela Santana Ramos; João Pedro Rueda Furlan; Inara Fernanda Lage Gallo; Lucas David Rodrigues dos Santos; Tatiana Amabile de Campos; Eduardo Angelino Savazzi; Eliana Guedes Stehling (Current Microbiology, 2020)

Fecal cultivable aerobic microbiota of dairy cows and calves acting as reservoir of clinically relevant antimicrobial resistance genes - João Pedro Rueda Furlan; Lucas David Rodrigues dos Santos; Micaela Santana Ramos; Inara Fernanda Lage Gallo; Eliana Guedes Stehling (Brazilian Journal of Microbiology, 2020)

Co-occurrence of mcr-1, mcr-3, mcr-7 and clinically relevant antimicrobial resistance genes in environmental and fecal samples - Lucas David Rodrigues dos Santos; João Pedro Rueda Furlan; Micaela Santana Ramos; Inara Fernanda Lage Gallo; Lucas Victor Pereira de Freitas; Eliana Guedes Stehling (Archives of Microbiology, 2020)

Productivity and Profitability of the Sugarcane Production in the State of Sao Paulo, Brazil - Fernando Rodrigues de Amorim; Marco Tulio Ospina Patino; Petra Maria Bartmeyer; David Ferreira Lopes Santos (Sugar Tech, 2020)

Changes in salivary protein composition of lambs supplemented with aerial parts and condensed tannins: extract from Cistus ladanifer L.—a preliminary study - Elsa Lamy; Lénia Rodrigues; Olinda Guerreiro; David Soldado; Alexandra Francisco; Monica Lima; Fernando Capela e Silva; Orlando Lopes; José Santos-Silva; Eliana Jerónimo (Agroforestry Systems, 2020)

Presence of Colistin Resistance mcr-4 Gene and Clinically Relevant Antimicrobial Resistance Genes in Sand Samples from a Public Beach - João Pedro Rueda Furlan; Lucas David Rodrigues dos Santos; Micaela Santana Ramos; Inara Fernanda Lage Gallo; Eliana Guedes Stehling (Water, Air, & Soil Pollution, 2020)

A method to analyze the relationship between locomotor activity and feeding behaviour in larvae of Betta splendens - José Gilmar da Silva Souza; Lais Teodoro Libeck; Bárbara do Carmo Rodrigues Virote; Renata Catão Egger; Gabriel Cândido Ribeiro de Sá; Gilmara Junqueira Machado; Luis David Solis Murgas (Aquaculture International, 2020)

Assessing ecological function in the context of species recovery - H. Resit Akçakaya; Ana S. L. Rodrigues; David A. Keith; E. J. Milner‐Gulland; Eric W. Sanderson; Simon Hedges; David P. Mallon; Molly K. Grace; Barney Long; Erik Meijaard; P. J. Stephenson (Conservation Biology, 2020)
Species interactions matter to conservation. Setting an ambitious recovery target for a species requires considering the size, density, and demographic structure of its populations such that they fulfill the interactions, roles, and functions of the species in the ecosystems in which they are embedded. A recently proposed framework for an International Union for Conservation of Nature Green List of Species formalizes this requirement by defining a fully recovered species in terms of representation, viability, and functionality. Defining and quantifying ecological function from the viewpoint of species recovery is challenging in concept and application, but also an opportunity to insert ecological theory into conservation practice. We propose 2 complementary approaches to assessing a species’ ecological functions: confirmation (listing interactions of the species, identifying ecological processes and other species involved in these interactions, and quantifying the extent to which the species contributes to the identified ecological process) and elimination (inferring functionality by ruling out symptoms of reduced functionality, analogous to the red‐list approach that focuses on symptoms of reduced viability). Despite the challenges, incorporation of functionality into species recovery planning is possible in most cases and it is essential to a conservation vision that goes beyond preventing extinctions and aims to restore a species to levels beyond what is required for its viability. This vision focuses on conservation and recovery at the species level and sees species as embedded in ecosystems, influencing and being influenced by the processes in those ecosystems. Thus, it connects and integrates conservation at the species and ecosystem levels.

Impacts of climate change on the evaporation and availability of water in small reservoirs in the Brazilian savannah - Daniel Althoff; Lineu Neiva Rodrigues; Demetrius David da Silva (Climatic Change, 2020)

Studies in Neotropical Araliaceae. I. Resurrection of the genus Sciodaphyllum P. Browne to accommodate most New World species previously included in Schefflera J. R. Forst. & G. Forst. - Porter P. Lowry II; Gregory M. Plunkett; M. Marcela Mora; Asunción Cano; Pedro Fiaschi; David G. Frodin; Roy E. Gereau; Álvaro Idárraga-Piedrahíta; Jáider Jiménez-Montoya; J. Moisés F. Mendoza; David A. Neill; Orlando Rivera-Diaz; et al. (Brittonia, 2020)

Spatial Variability of Soil Physicochemical Properties in Agricultural Fields Cultivated with Sugarcane (Saccharum officinarum L.) in Southeastern Mexico - Sergio Salgado-Velázquez; Sergio Salgado-García; Joaquín Alberto Rincón-Ramírez; Francelino Augusto Rodrigues; David Jesús Palma-López; Samuel Córdova-Sánchez; Antonio López-Castañeda (Sugar Tech, 2020)

Will the emblematic southern conifer Araucaria angustifolia survive to climate change in Brazil? - Monik Begname Castro; Ana Carolina Maioli Campos Barbosa; Patrícia Vieira Pompeu; Pedro V. Eisenlohr; Gabriel de Assis Pereira; Deborah Mattos Guimarães Apgaua; João Carlos Pires-Oliveira; João Paulo Rodrigues Alves Delfino Barbosa; Marco Aurélio Leite Fontes; Rubens Manoel dos Santos; David Yue Phin Tng (Biodiversity and Conservation, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Bridging the gap between will and action on climate change adaptation in large cities in Brazil - Gabriela Marques Di Giulio; Roger Rodrigues Torres; David M. Lapola; Ana Maria Bedran-Martins; Maria da Penha Vasconcellos; Diego Rafael Braga; Marcos Paulo Fuck; Yohanna Juk; Veruska Nogueira; Ana Carolina Penna; Tiago Jacaúna; Marcelo Fetz; et al. (Regional Environmental Change, 2019)

Bridging the gap between will and action on climate change adaptation in large cities in Brazil - Gabriela Marques Di Giulio; Roger Rodrigues Torres; David M. Lapola; Ana Maria Bedran-Martins; Maria da Penha Vasconcellos; Diego Rafael Braga; Marcos Paulo Fuck; Yohanna Juk; Veruska Nogueira; Ana Carolina Penna; Tiago Jacaúna; Marcelo Fetz; et al. (Regional Environmental Change, 2019)

Defining the indigenous ranges of species to account for geographic and taxonomic variation in the history of human impacts: reply to Sanderson 2019 - P. J. Stephenson; Molly K. Grace; H. Resit Akçakaya; Ana S. L. Rodrigues; Barney Long; David P. Mallon; Erik Meijaard; Jon Paul Rodriguez; Richard P. Young; Thomas M. Brooks; Craig Hilton‐Taylor (Conservation Biology, 2019)

Guidance for Rifampin and Midazolam Dosing Protocols To Study Intestinal and Hepatic Cytochrome P450 (CYP) 3A4 Induction and De-induction - Asha J Kapetas; Michael J Sorich; A David Rodrigues; Andrew Rowland (The AAPS Journal, 2019)

New GJA8 variants and phenotypes highlight its critical role in a broad spectrum of eye anomalies - Fabiola Ceroni; Domingo Aguilera-Garcia; Nicolas Chassaing; Dorine Arjanne Bax; Fiona Blanco-Kelly; Patricia Ramos; Maria Tarilonte; Cristina Villaverde; Luciana Rodrigues Jacy da Silva; Maria Juliana Ballesta-Martínez; Maria Jose Sanchez-Soler; Richard James Holt; et al. (Human Genetics, 2019)

Evaluating the Fit of Co-management for Small-Scale Fisheries Governance in Timor-Leste - Alexander Tilley; Kimberley J. Hunnam; David J. Mills; Dirk J. Steenbergen; Hugh Govan; Enrique Alonso-Poblacion; Matthew Roscher; Mario Pereira; Pedro Rodrigues; Teresa Amador; Agustinha Duarte; Mario Gomes; et al. (Frontiers in Marine Science, 2019)

Selenium and mercury concentration in drinking water and food samples from a coal mining area in Brazil - Marina Dos Santos; Flavio Manoel Rodrigues da Silva Júnior; David Vicente Zurdo; Paulo Roberto Martins Baisch; Ana Luíza Muccillo-Baisch; Yolanda Madrid (Environmental Science and Pollution Research, 2019)

Population structure and genetic relationships between Ethiopian and Brazilian Coffea arabica genotypes revealed by SSR markers - Bruna Silvestre Rodrigues da Silva; Gustavo César Sant’Ana; Camila Lucas Chaves; Leonardo Godoy Androcioli; Rafaelle Vecchia Ferreira; Gustavo Hiroshi Sera; Pierre Charmetant; Thierry Leroy; David Pot; Douglas Silva Domingues; Luiz Filipe Protasio Pereira (Genetica, 2019)

Incentives for aquaculture in protected areas: possible consequences for biodiversity and its services in southern Brazil - Jorge L. Rodrigues Filho; Débora Lugli-Bernardes; Lia Mayrink Sabinson; Rodrigo Machado; Harry Boos; Luciano Lorenzi; Marcelo Manoel Domingos; David Valença Dantas (Biodiversity and Conservation, 2019)

Isolation by instability: Historical climate change shapes population structure and genomic divergence of treefrogs in the Neotropical Cerrado savanna - Mariana M. Vasconcellos; Guarino R. Colli; Jesse N. Weber; Edgardo M. Ortiz; Miguel T. Rodrigues; David C. Cannatella (Molecular Ecology, 2019)
Although the impact of Pleistocene glacial cycles on the diversification of the tropical biota was once dismissed, increasing evidence suggests that Pleistocene climatic fluctuations greatly affected the distribution and population divergence of tropical organisms. Landscape genomic analyses coupled with paleoclimatic distribution models provide a powerful way to understand the consequences of past climate changes on the present‐day tropical biota. Using genome‐wide SNP data and mitochondrial DNA, combined with projections of the species distribution across the late Quaternary until the present, we evaluate the effect of paleoclimatic shifts on the genetic structure and population differentiation of Hypsiboas lundii , a treefrog endemic to the South American Cerrado savanna. Our results show a recent and strong genetic divergence in H. lundii across the Cerrado landscape, yielding four genetic clusters that do not seem congruent with any current physical barrier to gene flow. Isolation by distance (IBD) explains some of the population differentiation, but we also find strong support for past climate changes promoting range shifts and structuring populations even in the presence of IBD. Post‐Pleistocene population persistence in four main areas of historical stable climate in the Cerrado seems to have played a major role establishing the present genetic structure of this treefrog. This pattern is consistent with a model of reduced gene flow in areas with high climatic instability promoting isolation of populations, defined here as “isolation by instability,” highlighting the effects of Pleistocene climatic fluctuations structuring populations in tropical savannas.

No genetic differentiation, but less diversity, in the Iberian breeding population of the Eurasian Curlew (Numenius arquata) - Tiago M. Rodrigues; Pedro Andrade; María Vidal; Martin Boschert; David Gonçalves; Jesús Domínguez (Journal of Ornithology, 2019)

Topical Drug Delivery to the Posterior Segment of the Eye: Addressing the Challenge of Preclinical to Clinical Translation - Gerard A. Rodrigues; David Lutz; Jie Shen; Xiaoda Yuan; Hong Shen; James Cunningham; Hongwen M. Rivers (Pharmaceutical Research, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Aflatoxin B 1 and zearalenone in soybeans: occurrence and distribution in whole and defective kernels - Maria Antonia Calori-Domingues; Paula Municelli Rodrigues Iwahashi; Giancarlo Hercoton Ponce; Eduardo Micotti da Gloria; Carlos Tadeu dos Santos Dias; David Charles Button; Adriano Costa De Camargo (Food Additives & Contaminants Part B-Surveillance, 2018)

WASP nest: a worldwide assessment of social Polistine nesting behavior - Sara E. Miller; Sarah E. Bluher; Emily Bell; Alessandro Cini; Rafael Carvalho da Silva; André Rodrigues de Souza; Kristine M. Gandia; Jennifer Jandt; Kevin Loope; Amanda Prato; Jonathan N. Pruitt; David Rankin; et al. (Ecology, 2018)
Cooperative breeding decreases the direct reproductive output of subordinate individuals, but cooperation can be evolutionarily favored when there are challenges or constraints to breeding independently. Environmental factors, including temperature, precipitation, latitude, high seasonality, and environmental harshness have been hypothesized to correlate with the presence of cooperative breeding. However, to test the relationship between cooperation and ecological constraints requires comparative data on the frequency and variation of cooperative breeding across differing environments, ideally replicated across multiple species. Paper wasps are primitively social species, forming colonies composed of reproductively active dominants and foraging subordinates. Adult female wasps, referred to as foundresses, initiate new colonies. Nests can be formed by a single solitary foundress (noncooperative) or by multiple foundress associations (cooperative). Cooperative behavior varies within and among species, making paper wasps species well suited to disentangling ecological correlates of variation in cooperative behavior. This data set reports the frequency and extent of cooperative nest founding for 87 paper wasp species. Data were assembled from more than 170 published sources, previously unpublished field observations, and photographs contributed by citizen scientists to online natural history repositories. The data set includes 25,872 nest observations and reports the cooperative behavioral decisions for 45,297 foundresses. Species names were updated to reflect modern taxonomic revisions. The type of substrate on which the nest was built is also included, when available. A smaller population‐level version of this data set found that the presence or absence of cooperative nesting in paper wasps was correlated with temperature stability and environmental harshness, but these variables did not predict the extent of cooperation within species. This expanded data set contains details about individual nests and further increases the power to address the relationship between the environment and the presence and extent of cooperative breeding. Beyond the ecological drivers of cooperation, these high‐resolution data will be useful for future studies examining the evolutionary consequences of variation in social behavior. This data set may be used for research or educational purposes provided that this data paper is cited.

Quantifying species recovery and conservation success to develop an IUCN Green List of Species - H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Molly K. Grace; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; David A. Keith; Barney Long; David P. Mallon; Erik Meijaard; et al. (Conservation Biology, 2018)
Stopping declines in biodiversity is critically important, but it is only a first step toward achieving more ambitious conservation goals. The absence of an objective and practical definition of species recovery that is applicable across taxonomic groups leads to inconsistent targets in recovery plans and frustrates reporting and maximization of conservation impact. We devised a framework for comprehensively assessing species recovery and conservation success. We propose a definition of a fully recovered species that emphasizes viability, ecological functionality, and representation; and use counterfactual approaches to quantify degree of recovery. This allowed us to calculate a set of 4 conservation metrics that demonstrate impacts of conservation efforts to date (conservation legacy); identify dependence of a species on conservation actions (conservation dependence); quantify expected gains resulting from conservation action in the medium term (conservation gain); and specify requirements to achieve maximum plausible recovery over the long term (recovery potential). These metrics can incentivize the establishment and achievement of ambitious conservation targets. We illustrate their use by applying the framework to a vertebrate, an invertebrate, and a woody and an herbaceous plant. Our approach is a preliminary framework for an International Union for Conservation of Nature (IUCN) Green List of Species, which was mandated by a resolution of IUCN members in 2012. Although there are several challenges in applying our proposed framework to a wide range of species, we believe its further development, implementation, and integration with the IUCN Red List of Threatened Species will help catalyze a positive and ambitious vision for conservation that will drive sustained conservation action.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Monitoring of Francisella noatunensis subsp. orientalis in farmed Nile tilapia (Oreochromis niloticus) in Brazil - Marianna Vaz Rodrigues; Claire Juliana Francisco; Gianmarco S. David; Reinaldo José da Silva; Maria Fernanda Falcone-Dias; João Pessoa Araújo Júnior (Aquaculture International, 2018)

The invisibility of fisheries in the process of hydropower development across the Amazon - Carolina Rodrigues da Costa Doria; Simone Athayde; Elineide E. Marques; Maria Alice Leite Lima; Jynessa Dutka-Gianelli; Mauro Luis Ruffino; David Kaplan; Carlos E. C. Freitas; Victoria N. Isaac (Ambio, 2017)

Global patterns of interaction specialization in bird–flower networks - Thais B. Zanata; Bo Dalsgaard; Fernando C. Passos; Peter A. Cotton; James J. Roper; Pietro K. Maruyama; Erich Fischer; Matthias Schleuning; Ana M. Martín González; Jeferson Vizentin‐Bugoni; Donald C. Franklin; Stefan Abrahamczyk; et al. (Journal of Biogeography, 2017)
Aim Among the world's three major nectar‐feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources. Location Americas, Africa, Asia and Oceania/Australia. Methods We compiled interaction networks between birds and floral resources for 79 hummingbird, nine sunbird and 33 honeyeater communities. Interaction specialization was quantified through connectance ( C ), complementary specialization ( H 2 ′), binary ( Q B ) and weighted modularity ( Q ), with both observed and null‐model corrected values. We compared interaction specialization among the three types of bird–flower communities, both independently and while controlling for potential confounding variables, such as plant species richness, asymmetry, latitude, insularity, topography, sampling methods and intensity. Results Hummingbird–flower networks were more specialized than honeyeater–flower networks. Specifically, hummingbird–flower networks had a lower proportion of realized interactions (lower C ), decreased niche overlap (greater H 2 ′) and greater modularity (greater Q B ). However, we found no significant differences between hummingbird– and sunbird–flower networks, nor between sunbird– and honeyeater–flower networks. Main conclusions As expected, hummingbirds and their floral resources have greater interaction specialization than honeyeaters, possibly because of greater phenotypic specialization and greater floral resource richness in the New World. Interaction specialization in sunbird–flower communities was similar to both hummingbird–flower and honeyeater–flower communities. This may either be due to the relatively small number of sunbird–flower networks available, or because sunbird–flower communities share features of both hummingbird–flower communities (specialized floral shapes) and honeyeater–flower communities (fewer floral resources). These results suggest a link between interaction specialization and both phenotypic specialization and floral resource richness within bird–flower communities at a global scale.

Erratum to: Reliable Rate Measurements for Active and Passive Hepatic Uptake Using Plated Human Hepatocytes - Yi-an Bi; Renato J. Scialis; Sarah Lazzaro; Sumathy Mathialagan; Emi Kimoto; Julie Keefer; Hui Zhang; Anna M. Vildhede; Chester Costales; A. David Rodrigues; Larry M. Tremaine; Manthena V. S. Varma (The AAPS Journal, 2017)

Reliable Rate Measurements for Active and Passive Hepatic Uptake Using Plated Human Hepatocytes - Yi-an Bi; Renato J. Scialis; Sarah Lazzaro; Sumathy Mathialagan; Emi Kimoto; Julie Keefer; Hui Zhang; Anna M. Vildhede; Chester Costales; A. David Rodrigues; Larry M. Tremaine; Manthena V. S. Varma (The AAPS Journal, 2017)

Enhanced dietary formulation to mitigate winter thermal stress in gilthead sea bream (Sparus aurata): a 2D-DIGE plasma proteome study - Denise Schrama; Nadège Richard; Tomé S. Silva; Filipe A. Figueiredo; Luís E.C. Conceição; Richard Burchmore; David Eckersall; Pedro M.L. Rodrigues (Fish Physiology and Biochemistry, 2017)

Fighting Oxidative Stress: Increased Resistance of Male Rat Cerebellum at Weaning Induced by Low Omega 6/Omega 3 Ratio in a Protein-Deficient Diet - Ricielle Lopes Augusto; Alinny Rosendo Isaac; Ivanildo Inácio da Silva-Júnior; David Filipe de Santana; Diorginis José Soares Ferreira; Claudia Jacques Lagranha; Catarina Gonçalves-Pimentel; Marcelo Cairrão Araujo Rodrigues; Belmira Lara da Silveira Andrade-da-Costa (The Cerebellum, 2017)

Semi-autonomous inline water analyzer: design of a common light detector for bacterial, phage, and immunological biosensors - Elodie C.T. Descamps; Damien Meunier; Catherine Brutesco; Sandra Prévéral; Nathalie Franche; Ingrid Bazin; Bertrand Miclot; Philippe Larosa; Camille Escoffier; Jean-Raphael Fantino; Daniel Garcia; Mireille Ansaldi; et al. (Environmental Science and Pollution Research, 2017)

Bacterial host and reporter gene optimization for genetically encoded whole cell biosensors - Catherine Brutesco; Sandra Prévéral; Camille Escoffier; Elodie C. T. Descamps; Elsa Prudent; Julien Cayron; Louis Dumas; Manon Ricquebourg; Géraldine Adryanczyk-Perrier; Arjan de Groot; Daniel Garcia; Agnès Rodrigue; et al. (Environmental Science and Pollution Research, 2017)

Pushing the limits of nickel detection to nanomolar range using a set of engineered bioluminescent Escherichia coli - Julien Cayron; Elsa Prudent; Camille Escoffier; Erwan Gueguen; Marie-Andrée Mandrand-Berthelot; David Pignol; Daniel Garcia; Agnès Rodrigue (Environmental Science and Pollution Research, 2017)

Toward inline multiplex biodetection of metals, bacteria, and toxins in water networks: the COMBITOX project - Mireille Ansaldi; Ingrid Bazin; Pierre Cholat; Agnès Rodrigue; David Pignol (Environmental Science and Pollution Research, 2017)

Platelet Activating Factor (PAF) Receptor Deletion or Antagonism Attenuates Severe HSV-1 Meningoencephalitis - Márcia Carvalho Vilela; Graciela Kunrath Lima; David Henrique Rodrigues; Norinne Lacerda-Queiroz; Vinicius Sousa Pietra Pedroso; Aline Silva de Miranda; Milene Alvarenga Rachid; Erna Geessien Kroon; Marco Antônio Campos; Mauro Martins Teixeira; Antonio Lucio Teixeira (Journal of Neuroimmune Pharmacology, 2016)

IL-1β Is Involved with the Generation of Pain in Experimental Autoimmune Encephalomyelitis - David Henrique Rodrigues; Bruno Pereira Leles; Vivian Vasconcelos Costa; Aline Silva Miranda; Daniel Cisalpino; Dawidson Assis Gomes; Danielle Glória de Souza; Antônio Lúcio Teixeira (Molecular Neurobiology, 2016)

The last bastion? X chromosome genotyping of Anopheles gambiae species pair males from a hybrid zone reveals complex recombination within the major candidate ‘genomic island of speciation’ - Beniamino Caputo; Verena Pichler; Emiliano Mancini; Marco Pombi; José L. Vicente; Joao Dinis; Keith Steen; Vincenzo Petrarca; Amabelia Rodrigues; Joao Pinto; Alessandra della Torre; David Weetman (Molecular Ecology, 2016)
Speciation with gene flow may be aided by reduced recombination helping to build linkage between genes involved in the early stages of reproductive isolation. Reduced recombination on chromosome X has been implicated in speciation within the Anopheles gambiae complex, species of which represent the major Afrotropical malaria vectors. The most recently diverged, morphologically indistinguishable, species pair, A. gambiae and Anopheles coluzzii , ubiquitously displays a ‘genomic island of divergence’ spanning over 4 Mb from chromosome X centromere, which represents a particularly promising candidate region for reproductive isolation genes, in addition to containing the diagnostic markers used to distinguish the species. Very low recombination makes the island intractable for experimental recombination studies, but an extreme hybrid zone in Guinea Bissau offers the opportunity for natural investigation of X‐island recombination. SNP analysis of chromosome X hemizygous males revealed: (i) strong divergence in the X‐island despite a lack of autosomal divergence; (ii) individuals with multiple‐recombinant genotypes, including likely double crossovers and localized gene conversion; (iii) recombination‐driven discontinuity both within and between the molecular species markers, suggesting that the utility of the diagnostics is undermined under high hybridization. The largely, but incompletely protected nature of the X centromeric genomic island is consistent with a primary candidate area for accumulation of adaptive variants driving speciation with gene flow, while permitting some selective shuffling and removal of genetic variation.

Contrasting factors drive within-lake bacterial community composition and functional traits in a large shallow subtropical lake - Marla Sonaira Lima; David da Motta Marques; Ng Haig They; Katherine D. McMahon; Lúcia Ribeiro Rodrigues; Luciana de Souza Cardoso; Luciane Oliveira Crossetti (Hydrobiologia, 2016)

A spatially explicit estimate of the prewhaling abundance of the endangered North Atlantic right whale - Sophie Monsarrat; M. Grazia Pennino; Tim D. Smith; Randall R. Reeves; Christine N. Meynard; David M. Kaplan; Ana S.L. Rodrigues (Conservation Biology, 2016)
The North Atlantic right whale (NARW) (Eubalaena glacialis) is one of the world's most threatened whales. It came close to extinction after nearly a millennium of exploitation and currently persists as a population of only approximately 500 individuals. Setting appropriate conservation targets for this species requires an understanding of its historical population size, as a baseline for measuring levels of depletion and progress toward recovery. This is made difficult by the scarcity of records over this species’ long whaling history. We sought to estimate the preexploitation population size of the North Atlantic right whale and understand how this species was distributed across its range. We used a spatially explicit data set on historical catches of North Pacific right whales (NPRWs) (Eubalaena japonica) to model the relationship between right whale relative density and the environment during the summer feeding season. Assuming the 2 right whale species select similar environments, we projected this model to the North Atlantic to predict how the relative abundance of NARWs varied across their range. We calibrated these relative abundances with estimates of the NPRW total prewhaling population size to obtain high and low estimates for the overall NARW population size prior to exploitation. The model predicted 9,075–21,328 right whales in the North Atlantic. The current NARW population is thus

Thioridazine inhibits gene expression control of the cell wall signaling pathway (CWI) in the human pathogenic fungus Paracoccidioides brasiliensis - Daniela Leite Jabes; Ana Claudia de Freitas Oliveira; Valquíria Campos Alencar; Fabiano Bezerra Menegidio; Débora Liliane Souza Reno; Daiene Souza Santos; David Aciole Barbosa; Renata Ozelami Vilas Boas; Rodrigo Luiz de Oliveira Rodrigues Cunha; Tiago Rodrigues; Regina Costa de Oliveira; Luiz R. Nunes (Molecular Genetics and Genomics, 2016)

Binding of phenothiazines into allosteric hydrophobic pocket of human thioredoxin 1 - Eric Allison Philot; David da Mata Lopes; Aryane Tofanello de Souza; Antônio Sérgio Kimus Braz; Iseli Lourenço Nantes; Tiago Rodrigues; David Perahia; Maria A. Miteva; Luis Paulo Barbour Scott (European Biophysics Journal, 2016)

Biological activities of ophiobolin K and 6-epi-ophiobolin K produced by the endophytic fungus Aspergillus calidoustus - Camila Rodrigues de Carvalho; Mariana de Lourdes Almeida Vieira; Charles L. Cantrell; David E. Wedge; Tânia M.A. Alves; Carlos Leomar Zani; Raphael Sanzio Pimenta; Policarpo A. Sales Junior; Silvane M.F. Murta; Alvaro J. Romanha; Carlos Augusto Rosa; Luiz H. Rosa (Natural Product Research, 2016)

Environmental flow in the River Ondas basin in Bahia, Brazilian Cerrado - Elis Regina Rodrigues de Souza Castro; Michel Castro Moreira; Demetrius David da Silva (Environmental Monitoring and Assessment, 2016)

Fungi associated with rocks of the A tacama D esert: taxonomy, distribution, diversity, ecology and bioprospection for bioactive compounds - Vívian N. Gonçalves; Charles L. Cantrell; David E. Wedge; Mariana C. Ferreira; Marco Aurélio Soares; Melissa R. Jacob; Fabio S. Oliveira; Douglas Galante; Fabio Rodrigues; Tânia M. A. Alves; Carlos L. Zani; Policarpo A. S. Junior; et al. (Environmental Microbiology, 2016)
Summary This study assessed the diversity of cultivable rock‐associated fungi from A tacama D esert. A total of 81 fungal isolates obtained were identified as 29 Ascomycota taxa by sequencing different regions of DNA. C ladosporium halotolerans , P enicillium chrysogenum and P enicillium cf. citrinum were the most frequent species, which occur at least in four different altitudes. The diversity and similarity indices ranged in the fungal communities across the latitudinal gradient. The F isher‐α index displayed the higher values for the fungal communities obtained from the siltstone and fine matrix of pyroclastic rocks with finer grain size, which are more degraded. A total of 23 fungal extracts displayed activity against the different targets screened. The extract of P . chrysogenum afforded the compounds α‐linolenic acid and ergosterol endoperoxide, which were active against C ryptococcus neoformans and methicillin‐resistance S taphylococcus aureus respectively. Our study represents the first report of a new habitat of fungi associated with rocks of the A tacama D esert and indicated the presence of interesting fungal community, including species related with saprobes, parasite/pathogen and mycotoxigenic taxa. The geological characteristics of the rocks, associated with the presence of rich resident/resilient fungal communities suggests that the rocks may provide a favourable microenvironment fungal colonization, survival and dispersal in extreme conditions.

Relationships between sap-flow measurements, whole-canopy transpiration and reference evapotranspiration in field-grown papaya (Carica papaya L.) - Tiago Massi Ferraz; Alena Torres Netto; Fabrício De Oliveira Reis; Anderson Lopes Peçanha; Elias Fernandes De Sousa; José Altino Machado Filho; Weverton Pereira Rodrigues; David Michael Glenn; Eliemar Campostrini (Theoretical and Experimental Plant Physiology, 2015)

A Comparison of Independent Component Analysis (ICA) of fMRI and Electrical Source Imaging (ESI) in Focal Epilepsy Reveals Misclassification Using a Classifier - Danilo Maziero; Marcio Sturzbecher; Tonicarlo Rodrigues Velasco; Carlo Rondinoni; Agustin Lage Castellanos; David William Carmichael; Carlos Ernesto Garrido Salmon (Brain Topography, 2015)

The macroecology of phylogenetically structured hummingbird–plant networks - Ana M. Martín González; Bo Dalsgaard; David Nogués‐Bravo; Catherine H. Graham; Matthias Schleuning; Pietro K. Maruyama; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Severino Mendes de Azevedo; Andrea C. Baquero; et al. (Global Ecology and Biogeography, 2015)
Aim To investigate the association between hummingbird–plant network structure and species richness, phylogenetic signal on species' interaction pattern, insularity and historical and current climate. Location Fifty‐four communities along a c . 10,000 km latitudinal gradient across the A mericas (39° N –32° S ), ranging from sea level to c . 3700 m a.s.l., located on the mainland and on islands and covering a wide range of climate regimes. Methods We measured the level of specialization and modularity in mutualistic plant–hummingbird interaction networks. Using an ordinary least squares multimodel approach, we examined the influence of species richness, phylogenetic signal, insularity and current and historical climate conditions on network structure (null‐model‐corrected specialization and modularity). Results Phylogenetically related species, especially plants, showed a tendency to interact with a similar array of mutualistic partners. The spatial variation in network structure exhibited a constant association with species phylogeny ( R 2 = 0.18–0.19); however, network structure showed the strongest association with species richness and environmental factors ( R 2 = 0.20–0.44 and R 2 = 0.32–0.45, respectively). Specifically, higher levels of specialization and modularity were associated with species‐rich communities and communities in which closely related hummingbirds visited distinct sets of flowering species. On the mainland, specialization was also associated with warmer temperatures and greater historical temperature stability. Main conclusions Our results confirm the results of previous macroecological studies of interaction networks which have highlighted the importance of species richness and the environment in determining network structure. Additionally, for the first time, we report an association between network structure and species phylogenetic signal at a macroecological scale, indicating that high specialization and modularity are associated with high interspecific competition among closely related hummingbirds, subdividing the floral niche. This suggests a tighter co‐evolutionary association between hummingbirds and their plants than in previously studied plant–bird mutualistic systems.

Ichthyofauna of the Selvagens Islands. Do small coastal areas show high species richness in the northeastern Atlantic? - Frederico Almada; David Abecasis; David Villegas-Ríos; Sofia Henriques; Miguel P. Pais; Marisa Batista; Bárbara Horta e Costa; Joana Martins; Inês Tojeira; Nuno Vasco Rodrigues; Ricardo Araújo; Miguel Souto; et al. (Marine Biology Research, 2015)

Lake size and fish diversity in southern Brazil coastal lagoons - Ribeiro Rodrigues Lucia; Da Motta Marques David (Frontiers in Marine Science, 2015)

Kelps across the portuguese coast: evidence of top-down and bottom-up influences - Franco Joao; Wernberg Thomas; Bertocci Iacopo; Arenas Francisco; Martínez Brezo; Duarte Pedro; Jacinto David; Vasco-Rodrigues Nuno; Sousa-Pinto Isabel; Tuya Fernando (Frontiers in Marine Science, 2014)

Late Anxiety-Like Behavior and Neuroinflammation in Mice Subjected to Sublethal Polymicrobial Sepsis - Allan C. Calsavara; David H. Rodrigues; Aline S. Miranda; Priscila A. Costa; Cristiano X. Lima; Márcia C. Vilela; Milene A. Rachid; Antônio L. Teixeira (Neurotoxicity Research, 2013)

Modeling fecal contamination in the Aljezur coastal stream (Portugal) - Marta Rodrigues; Anabela Oliveira; Martha Guerreiro; André Bustorff Fortunato; José Menaia; Luís Mesquita David; Alexandra Cravo (Ocean Dynamics, 2011)

Zeuxine strateumatica (Orchidaceae) goes south: a first record for Brazil - Luiz Menini Neto; Marcelo Rodrigues Miranda; David Cruz (Kew Bulletin, 2011)

A Study of Gene Expression in the Nematode Resistant Wild Peanut Relative, Arachis stenosperma, in Response to Challenge with Meloidogyne arenaria - Patricia Messenberg Guimarães; Ana Cristina Miranda Brasileiro; Karina Proite; Ana Claudia Guerra de Araújo; Soraya Cristina Macedo Leal-Bertioli; Aline Pic-Taylor; Felipe Rodrigues da Silva; Carolina Vianna Morgante; Simone da Graça Ribeiro; David John Bertioli (Tropical Plant Biology, 2010)

Estimating parameters of a forest ecosystem C model with measurements of stocks and fluxes as joint constraints - Andrew D. Richardson; Mathew Williams; David Y. Hollinger; David J. P. Moore; D. Bryan Dail; Eric A. Davidson; Neal A. Scott; Robert S. Evans; Holly Hughes; John T. Lee; Charles Rodrigues; Kathleen Savage (Oecologia, 2010)

A method for detecting false bifurcations in dynamical systems: application to neural-field models - Serafim Rodrigues; David Barton; Frank Marten; Moses Kibuuka; Gonzalo Alarcon; Mark P. Richardson; John R. Terry (Biological Cybernetics, 2010)

Transitions to spike-wave oscillations and epileptic dynamics in a human cortico-thalamic mean-field model - Serafim Rodrigues; David Barton; Robert Szalai; Oscar Benjamin; Mark P. Richardson; John R. Terry (Journal of Computational Neuroscience, 2009)

The potential ecological costs and cobenefits of REDD: a critical review and case study from the Amazon region - CLAUDIA M. STICKLER; DANIEL C. NEPSTAD; MICHAEL T. COE; DAVID G. McGRATH; HERMANN O. RODRIGUES; WAYNE S. WALKER; BRITALDO S. SOARES‐FILHO; ERIC A. DAVIDSON (Global Change Biology, 2009)
The United Nations climate treaty may soon include a mechanism for compensating tropical nations that succeed in reducing carbon emissions from deforestation and forest degradation, source of nearly one fifth of global carbon emissions. We review the potential for this mechanism [reducing emissions from deforestation and degradation (REDD)] to provoke ecological damages and promote ecological cobenefits. Nations could potentially participate in REDD by slowing clear‐cutting of mature tropical forest, slowing or decreasing the impact of selective logging, promoting forest regeneration and restoration, and expanding tree plantations. REDD could also foster efforts to reduce the incidence of forest fire. Potential ecological costs include the accelerated loss (through displaced agricultural expansion) of low‐biomass, high‐conservation‐value ecosystems, and substitution of low‐biomass vegetation by monoculture tree plantations. These costs could be avoided through measures that protect low‐biomass native ecosystems. Substantial ecological cobenefits should be conferred under most circumstances, and include the maintenance or restoration of (1) watershed functions, (2) local and regional climate regimes, (3) soils and biogeochemical processes, (4) water quality and aquatic habitat, and (5) terrestrial habitat. Some tools already being developed to monitor, report and verify (MRV) carbon emissions performance can also be used to measure other elements of ecosystem function, making development of MRV systems for ecological cobenefits a concrete possibility. Analysis of possible REDD program interventions in a large‐scale Amazon landscape indicates that even modest flows of forest carbon funding can provide substantial cobenefits for aquatic ecosystems, but that the functional integrity of the landscape's myriad small watersheds would be best protected under a more even spatial distribution of forests. Because of its focus on an ecosystem service with global benefits, REDD could access a large pool of global stakeholders willing to pay to maintain carbon in forests, thereby providing a potential cascade of ecosystem services to local stakeholders who would otherwise be unable to afford them.

Projection of Exposure and Efficacious Dose Prior to First-in-Human Studies: How Successful Have We Been? - Christine Huang; Ming Zheng; Zheng Yang; A. David Rodrigues; Punit Marathe (Pharmaceutical Research, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Hypermethylation of Cyclin D2 is associated with loss of mRNA expression and tumor development in prostate cancer - Rui Henrique; Vera Lúcia Costa; Nuno Cerveira; André Lopes Carvalho; Mohammad Obaidul Hoque; Franclim Ricardo Ribeiro; Jorge Oliveira; Manuel Rodrigues Teixeira; David Sidransky; Carmen Jerónimo (Journal of Molecular Medicine, 2006)

Characterization of Exiguobacterium isolates from the Siberian permafrost. Description of Exiguobacterium sibiricum sp. nov. - Debora Frigi Rodrigues; Johan Goris; Tatiana Vishnivetskaya; David Gilichinsky; Michael F. Thomashow; James M. Tiedje (Extremophiles, 2006)

QTLs and candidate genes for wood properties in maritime pine (Pinus pinaster Ait.) - David Pot; Jose-Carlos Rodrigues; Philippe Rozenberg; Guillaume Chantre; Josquin Tibbits; Christine Cahalan; Frédérique Pichavant; Christophe Plomion (Tree Genetics & Genomes, 2006)

Historical Evidence of Widespread Chytrid Infection in North American Amphibian Populations - MARTIN OUELLET; IGOR MIKAELIAN; BRUCE D. PAULI; JEAN RODRIGUE; DAVID M. GREEN (Conservation Biology, 2005)
Emerging infectious diseases may be contributing to the global decline of amphibian populations. In particular, chytridiomycosis, a cutaneous fungal infection of amphibians caused by the chytrid Batrachochytrium dendrobatidis , gained attention in the 1990s as an apparently new pathogen. This fungus has been implicated as the causative agent of widespread mortalities among wild amphibians in geographically disparate parts of the world. To investigate the global distribution, historical occurrence, and infectiousness of this pathogen, we examined 3371 postmetamorphic and adult amphibians collected between 1895 and 2001 from 25 countries for the presence of chytrid fungi in the epidermis. Cutaneous chytrid infection was diagnosed in 383 of 2931 (13.1%) specimens of 12 common amphibian species from five Canadian provinces and seven American states, including 30 of 69 locations examined in the St. Lawrence River Valley of Québec. Chytrids were observed in 7.0% (46/655) of the adults collected in the 1960s, the earliest cases being two green frogs ( Rana clamitans ) collected in 1961 from Saint‐Pierre‐de‐Wakefield, Québec. In recent studies, morbidity and mortality attributable to chytridiomycosis were not observed in infected amphibians from Québec despite a 17.8% (302/1698) prevalence of chytrid infection during the period 1990–2001. The prevalence of infection during this latter period was not statistically different when compared with the period 1960–1969. Epidermal chytrid infections were not observed in 440 amphibians examined from 23 other countries. In light of the fact that infection by B. dendrobatidis is widely distributed and apparently enzootic in seemingly healthy amphibians from eastern North America, lethal outbreaks of chytridiomycosis among amphibian populations appear to have complex causes and may be the result of underlying predisposing factors.

Changes in Carbon Storage and Net Carbon Exchange One Year After an Initial Shelterwood Harvest at Howland Forest, ME - Neal A. Scott; Charles A. Rodrigues; Holly Hughes; John T. Lee; Eric A. Davidson; D. Bryan Dail; Phil Malerba; David Y. Hollinger (Environmental Management, 2004)

Characterization of the Ecdysteroid UDP-Glucosyltransferase (egt) Gene of Anticarsia gemmatalis Nucleopolyhedrovirus - Júlio Carlyle Macedo Rodrigues; Marlinda Lobo De Souza; David O'reilly; Lucas Malard Velloso; Francisco José Rivera Pinedo; Fernando Barcellos Razuck; Berghem Ribeiro; Bergmann Morais Ribeiro (Virus Genes, 2001)

Molecular characterisation of a NADH ubiquinone oxidoreductase subunit 5 from Schistosoma mansoni and inhibition of mitochondrial respiratory chain function by testosterone - Marcelo Rosado Fantappié; Antônio Galina; Ricardo Luís de Mendonça; Daniel Rodrigues Furtado; W. Evan Secor; Daniel G. Colley; Rodrigo Corrêa-Oliveira; George Freeman; Antônio Jorge Tempone; Lia Lannes de Camargo; Franklin David Rumjanek (Molecular and Cellular Biochemistry, 1999)

Preclinical Drug Metabolism in the Age of High-Throughput Screening: An Industrial Perspective - A. David Rodrigues (Pharmaceutical Research, 1997)